Adhesive composition and methods of forming the same
By introducing a composition of graft copolymer and a specific component ratio into the pressure-sensitive adhesive, the problem of insufficient adhesion and stability of the pressure-sensitive adhesive on the thermoplastic rubber material in the prior art is solved, and higher adhesion and long-term stability are achieved.
Patent Information
- Application Number
- JP2024226444
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-12-28
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When existing pressure-sensitive adhesives are attached to thermoplastic rubber materials, they lack sufficient cohesion and long-term stability, resulting in poor adhesion performance.
A pressure sensitive glue composition containing a graft copyright polymer is used, which contains micro-components, 50% to 98% of (meth) propionate polymer, 0.1% to 30% of the resin component, and has a molecular weight of about 1000 g/mol and a glass transition temperature of 40°C or above.
The adhesion and long-term stability of pressure-sensitive adhesive on thermoplastic rubber materials are improved, ensuring high-performance adhesive effect.
Smart Images

Figure 2025060780000011 
Figure 2025060780000012 
Figure 2025060780000013
Abstract
Description
[Technical field]
[0001] The present disclosure relates to adhesive compositions and methods of forming same. The present invention further relates to a foam tape comprising the same and a method for forming the same. [Background technology]
[0002] Pressure sensitive adhesives are used in many industrial and consumer markets to attach a variety of substrates. Depending on the specific application, pressure sensitive adhesives are designed to be either single layer or multi-layer. The substrates may be of similar nature or very different nature. The substrates of this type are, in particular, those on one side of which the substrate is polypropylene and polypropylene / ethylene. When made from thermoplastic olefins, including propylene diene terpolymers, Typically, adhesives designed for these thermoplastic materials tend to be more difficult to apply. These pressure sensitive adhesives tend to lack sufficient cohesive strength as well as long term stability. The problem is that a pressure sensitive adhesive needs to possess both high adhesive strength and high cohesiveness, This is even more important in applications where exposure to the elements is expected for many years in reality. Thus, it retains high overall performance over thermoplastic olefins even after years of exposure. There is a strong need to develop pressure sensitive adhesives. Summary of the Invention
[0003] According to a first aspect, the adhesive may comprise an adhesive structure and an adhesive composition. The structure may include a graft copolymer. The adhesive composition may include, by weight of the total adhesive composition, At least about 1% by weight and no more than 40% by weight of a micro monomer component and an adhesive composition. At least about 50% by weight and no more than about 98% by weight (meth)acrylic acid, based on the total weight of the composition. and at least about 0.1 wt. % of the total weight of the adhesive composition. and about 30% by weight or less of a tackifier component. Both have a weight average molecular weight of 1000 g / mol and a glass transition temperature of at least about 40° C. The (meth)acrylic polymer component A may have a glass transition temperature (Tg) of about 20° C. or less. It may have a temperature (Tg).
[0004] According to yet another aspect, a method of forming an adhesive includes providing a pre-adhesive mixture. and mixing the pre-adhesive mixture to form an adhesive. and polymerizing the pre-adhesive mixture. at least about 1% by weight and no more than 40% by weight of a pre-adhesive micro-monomer component; At least about 50% by weight and no more than about 98% by weight of the total weight of the adhesive mixture. Adhesive (meth)acrylic polymer component A and pre-adhesive mixture, based on the total weight of the mixture at least about 0.1% by weight and no more than about 30% by weight of a pre-adhesive tackifier component; The pre-adhesive macromonomer component has a weight average molecular weight of at least 1000 g / mol. and a glass transition temperature (Tg) of at least about 40° C. The acrylic polymer component A may have a glass transition temperature (Tg) of about 20° C. or less. The adhesive formed by polymerizing the adhesive mixture is a structure and an adhesive The adhesive construction may comprise a graft copolymer.
[0005] According to yet another aspect, the single layer foam tape includes hollow microspheres in the adhesive. The adhesive may include an adhesive structure and an adhesive composition. The structure may include a graft copolymer. The adhesive composition may include, by weight of the total adhesive composition, At least about 1% by weight and no more than 40% by weight of a micro monomer component and an adhesive composition. At least about 50% by weight and no more than about 98% by weight (meth)acrylic acid, based on the total weight of the composition. and at least about 0.1 wt. % of the total weight of the adhesive composition. and about 30% by weight or less of a tackifier component. Both have a weight average molecular weight of 1000 g / mol and a glass transition temperature of at least about 40° C. The (meth)acrylic polymer component A may have a glass transition temperature (Tg) of about 20° C. or less. It may have a temperature (Tg).
[0006] According to yet another aspect, the foam tape includes a foam core and a first portion of the foam core. The foam core may include a first adhesive layer of a first adhesive covering a surface of the foam material. The first adhesive may include hollow microspheres in the material. The first adhesive may include a first adhesive structure and a first adhesive. The first adhesive structure may comprise a graft copolymer. The adhesive composition comprises at least about 1% by weight and 40% by weight of the first adhesive composition. % by weight or less of a first micro-monomer component and at least about 50% by weight and no more than about 98% by weight of a first (meth)acrylic polymer component A and at least about 0.1 wt. % and about 30 wt. % based on the total weight of the first adhesive composition. and a first tackifier component in an amount of at least about 100% by weight. Both have a weight average molecular weight of 1000 g / mol and a glass transition temperature of at least about 40° C. The first (meth)acrylic polymer component A may have a glass transition temperature (Tg) of about 20° C. or less. The material may have a transition temperature (Tg). [Brief description of the drawings]
[0007] Embodiments are illustrated by way of example and not limitation in the accompanying figures.
[0008] [Figure 1] 1 includes diagrams illustrating methods of forming adhesive compositions according to embodiments described herein. [Diagram 2] 1 includes illustrative diagrams showing the construction of a single layer foam tape formed according to embodiments described herein. [Diagram 3] 1 includes an illustrative diagram showing the construction of a foam tape having a single adhesive layer formed according to embodiments described herein. [Figure 4] 1 includes an illustrative diagram showing the construction of a foam tape having two adhesive layers formed according to embodiments described herein.
[0009] Skilled artisans will appreciate that elements in the figures are illustrated for simplicity and clarity and are not necessarily drawn to scale. They understand that the world is not depicted in the way it is. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The following discussion will focus on specific implementations and embodiments of the present teachings. This description is provided to help explain certain embodiments and is not intended to be limiting of the present disclosure and They should not be construed as limitations on the scope or applicability of the present teachings. It is understood that these can be used based on the disclosure and teachings provided herein. It will be understood.
[0011] The terms "comprises," "comprising," and "including "includes," "including," "has," "Having," or any other variation thereof, is intended to include a non-exclusive inclusion. For example, a method, article, or apparatus that comprises a list of features does not necessarily represent those features. is not limited to features not expressly listed in such method, article, or apparatus. Furthermore, unless expressly stated otherwise, the present invention may include other features not inherent thereto. Unless otherwise stated, "or" refers to an inclusive "or" and not an exclusive "or." For example, condition A or B can be satisfied by any one of the following: A is true (or exists) and B is false (or does not exist), A is false (or exists) and B is A is not true (or exists) and B is true (or exists), and A and B are both true (or exist). do.
[0012] Additionally, the use of "a" or "an" refers to any element or elements described herein. This is done merely for convenience and to provide a general idea of the scope of the invention. This specification refers to one, two, or three parts unless it is clear that another is meant. The singular form must be read to include at least one, or the plural, or vice versa. For example, where a single item is described herein, a plurality of items may be used in place of the single item. Similarly, where a plurality of items is described herein, the following may be used in place of the plurality of items: A single article may be used.
[0013] The embodiments described herein generally relate to adhesive compositions and methods for forming the adhesive compositions. and more particularly, an adhesive composition having excellent adhesive properties and a method for forming the same - Patents.com Regarding.
[0014] For illustrative purposes, FIG. 1 illustrates an adhesive composition formulation according to certain embodiments described herein. The adhesive composition forming method 100 includes providing a pre-adhesive mixture. The method includes a first step 110 of mixing a pre-adhesive mixture, a second step 120 of mixing a pre-adhesive mixture, and a second step 130 of mixing an adhesive composition. and a third step 130 of polymerizing the pre-adhesive mixture to form the article.
[0015] Referring to the first step 110, according to one embodiment, a pre-adhesive mixture is Adhesive macromonomer component, a pre-adhesive (meta) that is partially polymerized before being added to the mixture. ) an acrylic polymer component A, and a pre-adhesive tackifier component.
[0016] According to certain embodiments, the pre-adhesive macromonomer component has a high glass transition temperature (T According to yet another embodiment, the pre-adhesive macromonomer may be referred to as having The mer component may have a particular glass transition temperature as predicted by the Fox equation. For example, the pre-adhesive macromonomer component may be cured at a temperature of at least about 40° C., e.g., at least about 45°C, or at least about 50°C, or at least about 55°C, or at least about 6 0° C., or at least about 65° C., or at least about 70° C., or at least about 75° C. °C, or at least about 80 °C, or at least about 85 °C, or at least about 95 °C , or at least about 100° C., or at least about 105° C., or at least about 11 0° C., or at least about 115° C., or at least about 120° C., or at least about It may have a glass transition temperature (Tg) of 125°C, or even at least about 130°C. The glass transition temperature of the adhesive macromonomer component is within a range between any of the values stated above. The glass transition temperature of the pre-adhesive macromonomer component may be between any of the values listed above. It will further be appreciated that it can be any value.
[0017] According to yet another embodiment, the pre-adhesive macromonomer component has a specific molecular weight. For example, the pre-adhesive macromonomer component may have a molecular weight of at least about 1,000 g / mol. For example, at least about 5,000 g / mol, or at least about 10,000 g / mol l, or at least about 15,000 g / mol, or at least about 20,000 g / mol mol, or at least about 25,000 g / mol, or at least about 30,000 According to yet another embodiment, the pre-adhesive macromonomer may have a molecular weight of 1000 g / mol. - component is about 100,000 g / mol or less, for example, about 75,000 g / mol or less, Alternatively, the pre-adhesive macromonomer composition may have a molecular weight of about 50,000 g / mol or less. It is understood that the molecular weight of the moiety can be within a range between any of the minimum and maximum values recited above. The pre-adhesive macromonomer component may be any value between any of the minimum and maximum values set forth above. It will be further appreciated that the value may be
[0018] According to yet another embodiment, the pre-adhesive mixture comprises a specific content of pre-adhesive macromolecules. For example, a pre-adhesive macromonomer component in the pre-adhesive mixture may include a monomer component. The content of is at least about 2.0% by weight, for example, based on the total weight of the pre-adhesive mixture. At least about 3.0% by weight, or at least about 4.0% by weight, or at least about 5. 0% by weight, or at least about 6.0% by weight, or at least about 7.0% by weight, or At least about 8.0% by weight, or at least about 9.0% by weight, or at least about 10 0.0% by weight, or at least about 12.5% by weight, or at least about 15.0% by weight, or at least about 17.5% by weight, or at least about or even at least about 20 According to yet another embodiment, the pre-adhesive in the pre-adhesive mixture may be 0.0% by weight. The content of the macromonomer component is about 40.0% by weight or less based on the total weight of the pre-adhesive. For example, about 39% by weight or less, or about 38% by weight or less, or about 37% by weight or less, or About 36% by weight or less, or about 35% by weight or less, or about 34% by weight or less, or about 33% by weight or less % by weight or less, or about 32% by weight or less, or about 31% by weight or less, or about 30% by weight or less or about 29% by weight or less, or about 28% by weight or less, or about 27% by weight or less, or The amount of the pre-adhesive in the pre-adhesive mixture may be about 26% by weight or less, or even about 25% by weight or less. The content of the adhesive macromonomer component may be within a range between any of the minimum and maximum values set forth above. It will be understood that the pre-adhesive macromonomer components in the pre-adhesive mixture may be It is further understood that the content of the moiety may be any value between any of the minimum and maximum values set forth above. It will be understood.
[0019] According to yet another embodiment, the pre-adhesive macromonomer component is a reversible deactivatable polymer. Advantageously, this can be achieved through the use of radical polymerization (RDRP) or controlled radical polymerization (CRP) techniques. Examples of these polymerization techniques include nitroxide mediated polymerization. Radical polymerization (NMP), reversible addition-fragmentation chain transfer polymerization (RAFT), atom transfer radical polymerization (ATRP), and cobalt-mediated catalytic chain transfer polymerization (CCT). According to another embodiment, the macromonomer component is cyclohexyl acrylate, cyclohexyl acrylate, Hexyl methacrylate, isobornyl acrylate, isobornyl methacrylate, di Cyclopentanyl acrylate, dicyclopentanyl methacrylate, 1-adamantyl With pendant alicyclic functional groups such as acrylate, 1-adamantyl methacrylate, etc. According to yet another embodiment, the pre-adhesive mac- may contain a (meth)acrylic monomer. The promonomer component may contain a terminal vinyl double bond. The adhesive macromonomer component can be polymerized in a free radical polymerization process. It may be possible.
[0020] According to a particular embodiment, the pre-adhesive (meth)acrylic polymer component A has a low glass content. According to yet another embodiment, the pre-bonding may be referred to as having a transition temperature (Tg). The (meth)acrylic polymer component A is a homopolymer of the constituent monomers, and its Tg and Specific glass transition, as estimated by the Fox equation, based on weight percent For example, the pre-adhesive (meth)acrylic polymer component A may have a temperature (Tg) of about 20° C. or less, for example, about 15° C. or less, or about 10° C. or less, or about 5° C. or less, The pre-adhesive (meth)acrylic polyimide may have a glass transition temperature (Tg) of about 0° C. or less. It will be understood that the polymer component A can range between any of the values recited above. The glass transition temperature of the pre-adhesive (meth)acrylic polymer component A is any one of the above. It will be further understood that the value may be any value between the values.
[0021] According to yet another embodiment, the pre-adhesive mixture comprises a specific content of pre-adhesive (meta ) acrylic polymer component A. For example, the pre-adhesive (metal) in the pre-adhesive mixture may contain p) The acrylic polymer component A is at least about 5% by weight based on the total weight of the pre-adhesive mixture. 0.0% by weight, for example, at least about 52% by weight, or at least about 55% by weight, is at least about 57% by weight, or at least about 60.0% by weight, or at least about 6 2% by weight, or at least about 65% by weight, or at least about 67% by weight, or less At least about 70.0%, or at least about 72%, or at least about 75% by weight %, or even at least about 77% by weight. The content of pre-adhesive (meth)acrylic polymer component A in the adhesive mixture is about 90.0% by weight or less, for example, about 88% by weight or less, based on the total weight of the mixture of agents; about 85% by weight or less, or about 83% by weight or less, or about 80% by weight or less, or even about The pre-adhesive (meth)acrylic polymer in the pre-adhesive mixture may be up to 78% by weight. It is understood that the content of component A can be within a range between any of the minimum and maximum values set forth above. The amount of pre-adhesive (meth)acrylic polymer component A in the pre-adhesive mixture will be It is further understood that the content can be any value between any of the minimum and maximum values stated above. It will be possible.
[0022] According to yet another embodiment, the pre-adhesive (meth)acrylic polymer component A is It may comprise the reaction product of adhesive monomer component a1 and pre-adhesive monomer component a2. According to one embodiment, the pre-adhesive monomer component a1 is an ethylenically unsaturated monomer. According to one embodiment, the ethylenically unsaturated monomer is an acid-containing (meth)acrylic Monomers (acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, etc.), hydrochloric acid, hydroxy-containing (meth)acrylic monomer (2-hydroxyethyl (meth)acrylate), Nitrogen-containing monomers having primary, secondary, or tertiary amino groups, and primary, secondary The monomer may be selected from the group consisting of nitrogen-containing monomers having a primary, secondary, or tertiary amide group.
[0023] According to yet another embodiment, the pre-adhesive monomer component a2 is an acrylate ester. According to yet another embodiment, the pre-adhesive monomer component a2 is of the formula C=C (R 2 )(COOR 1 wherein R1 is an acrylic acid ester having a formula of 1 to 24 is an alkyl group containing 1 to 2 carbon atoms, and R2 is H or methyl.
[0024] According to yet another embodiment, the pre-adhesive (meth)acrylic polymer component A is For example, the pre-adhesive (meth)acrylic monomer component a1 may contain The content of the pre-adhesive monomer component a1 in the vinyl polymer component A is At least about 0.1% by weight, for example at least At least about 0.5% by weight, or at least about 1.0% by weight, or at least about 1.5% by weight %, or at least about 2.0% by weight, or at least about 2.5% by weight, or less At least about 3.0% by weight, or at least about 3.5% by weight, or at least about 4.0% by weight %, or at least about 4.5% by weight, or at least about 5.0% by weight, or less At least about 5.5% by weight, or even at least about 6.0% by weight. According to an embodiment, the pre-adhesive monomer in the pre-adhesive (meth)acrylic polymer component A The content of component a1 is based on the total weight of pre-adhesive (meth)acrylic polymer component A. About 10% by weight or less, for example, about 9.5% by weight or less, or about 9.0% by weight or less, or 8.5% by weight or less, or about 8.0% by weight or less, or about 7.5% by weight or less, or about 7 .0% by weight or less, or about 6.5% by weight or less, or about 6.0% by weight or less, or about 5. 5% by weight or less, or about 5.0% by weight or less, or about 4.5% by weight or less, or about 4.0 % by weight or less, or about 3.5% by weight or less, or even about 3.0% by weight or less. Content of pre-adhesive monomer component a1 in pre-adhesive (meth)acrylic polymer component A It will be understood that may be in a range between any of the minimum and maximum values stated above. Content of pre-adhesive monomer component a1 in pre-adhesive (meth)acrylic polymer component A It will be further understood that may be any value between any of the minimum and maximum values stated above. There will be.
[0025] According to yet another embodiment, the pre-adhesive (meth)acrylic polymer component A is For example, the pre-adhesive (meth)acrylic monomer component a2 may contain The content of the pre-adhesive monomer component a2 in the vinyl polymer component A is At least about 80% by weight, for example at least or at least about 82%, or at least about 85%, or at least about 87%, At least about 90% by weight, or at least about 92% by weight, or at least about 95% by weight % by weight, or at least about 97% by weight. The content of the pre-adhesive monomer component a2 in the adhesive (meth)acrylic polymer component A is ( Based on the total weight of the meth)acrylic polymer component A, it can be up to about 99.0 wt %. The content of the monomer component a2 in the (meth)acrylic polymer component A is any minimum amount as described above. It will be understood that the range may be between the above and maximum values. The content of the monomer component a2 in the polymer component A may be any value between the minimum and maximum values described above. It will be further understood that the values may be any values.
[0026] According to one embodiment, the pre-adhesive tackifier component is selected from the group consisting of C5, C9, C5 / C9, diphenyl ether, ... Cyclopentadiene, terpene, or hydrogenated resins thereof, or combinations thereof may include.
[0027] According to yet another embodiment, the pre-adhesive mixture comprises a specific content of pre-adhesive tackifier. For example, the content of the pre-adhesive tackifier component in the pre-adhesive mixture may be is at least 0.1% by weight, for example at least about 0.5% by weight, or at least about 1.0% by weight, or at least about 1.5% by weight, or at least about 2.0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight, or at least about 3.5% by weight, or at least about 4.0% by weight; or at least about 4.5% by weight, or at least about 5.0% by weight, or at least about 5.5% by weight, or at least about 6.0% by weight, or at least about 6.5% by weight; or at least about 7.0% by weight, or at least about 7.5% by weight, or at least about 8.0% by weight, or at least about 8.5% by weight, or at least about 9.0% by weight, or at least about 9.5%, or even at least about 10.0% by weight. According to yet another embodiment, the inclusion of a pre-adhesive tackifier component in the pre-adhesive mixture The amount is about 30% by weight or less, for example about 25% by weight or less, based on the total weight of the pre-adhesive mixture. or less than about 20% by weight, or less than about 18% by weight, or less than about 15% by weight, The pre-adhesive in the pre-adhesive mixture may be about 13% by weight or less, or about 11% by weight or less. The content of the adhesive tackifier component can be within a range between any of the minimum and maximum values mentioned above. It will be understood that the content of the pre-adhesive tackifier component in the pre-adhesive mixture is It will be further understood that the value of β can be any value between any of the minimum and maximum values stated above. Wax.
[0028] With reference to the adhesive formed according to the embodiments described herein, the adhesive may include a particular According to yet another embodiment, the adhesive composition may include a macromonomer. - Component, a (meth)acrylic polymer that is partially polymerized before being added to the adhesive composition It may include component A, and a tackifier component.
[0029] According to certain embodiments, the macromonomer component has a high glass transition temperature (Tg). According to yet another embodiment, the macromonomer component may be referred to as Based on the Tg of the homopolymer of the mer and its weight percent, the Fox equation was used to predict For example, the macromonomer composition may have a specific glass transition temperature (Tg) as determined by the The heating time is at least about 40° C., e.g., at least about 45° C., or at least about 50° C. or at least about 55°C, or at least about 60°C, or at least about 65°C, or at least about 70° C., or at least about 75° C., or at least about 80° C., at least about 85° C., or at least about 95° C., or at least about 100° C., is at least about 105°C, or at least about 110°C, or at least about 115°C; or at least about 120° C., or at least about 125° C., or even at least about The glass transition temperature (Tg) of the macromonomer component may be 130° C. The glass transition temperature of the macromonomer component can be in the range between any of the values mentioned above. , it will be further understood that the value may be any value between any of the values stated above.
[0030] According to yet another embodiment, the macromonomer component may have a specific molecular weight. For example, the macromonomer component may have a molecular weight of at least about 1,000 g / mol, e.g., at least about 5,000 g / mol, or at least about 10,000 g / mol, or at least About 15,000 g / mol, or at least about 20,000 g / mol, or less Both have a molecular weight of about 25,000 g / mol, or at least about 30,000 g / mol. According to yet another embodiment, the macromonomer component may have a molecular weight of about 100,000 g / mol. mol or less, for example, about 75,000 g / mol or less, or about 50,000 g / mol or less. The molecular weight of the macromonomer component may be any of the minimum and maximum values set forth above. It will be understood that the macromonomer component may be in the range between 0.1 and 1.0. It will be further understood that the minimum and maximum values may be any value between these minimum and maximum values.
[0031] According to yet another embodiment, the pre-adhesive composition contains a specific content of macromonomer components. For example, the content of the macromonomer component in the adhesive composition may be At least about 2.0% by weight, for example at least about 3.0% by weight, based on the total weight of the composition. or at least about 4.0% by weight, or at least about 5.0% by weight, or at least about 6.0% by weight, or at least about 7.0% by weight, or at least about 8.0% by weight, or at least about 9.0%, or at least about 10.0%, or at least About 12.5% by weight, or at least about 15.0% by weight, or at least about 17.5% by weight %, or at least about, or even at least about 20.0% by weight. According to another embodiment, the content of the macromonomer component in the adhesive composition is About 40.0% by weight or less, for example, about 39% by weight or less, or about 38% by weight or less, based on the total weight of the % by weight or less, or about 37% by weight or less, or about 36% by weight or less, or about 35% by weight or less or about 34% by weight or less, or about 33% by weight or less, or about 32% by weight or less, or About 31% by weight or less, or about 30% by weight or less, or about 29% by weight or less, or about 28% by weight or less % by weight or less, or about 27% by weight or less, or about 26% by weight or less, or even about 25% by weight or less The content of the macromonomer component in the adhesive composition may be any minimum of the above. It will be understood that the amount of the carboxyl group in the adhesive composition may be within a range between the above and maximum values. The content of the monomer component may be any value between any of the minimum and maximum values mentioned above. It will be further understood.
[0032] According to yet another embodiment, the macromonomer component is polymerized by reversible deactivation radical polymerization. can be advantageously synthesized through the use of controlled radical polymerization (RDRP) or controlled radical polymerization (CRP) techniques; Examples of these polymerization techniques include nitroxide mediated radical polymerization. (NMP), reversible addition-fragmentation chain transfer polymerization (RAFT), atom transfer radical polymerization (AT Catalytic Chain Transfer Polymerization (RP), and Cobalt-Mediated Catalytic Chain Transfer Polymerization (CCT). According to the form, the macromonomer component is cyclohexyl acrylate, cyclohexyl methacrylate, acrylate, isobornyl acrylate, isobornyl methacrylate, dicyclopentasiloxane Dicyclopentanyl acrylate, dicyclopentanyl methacrylate, 1-adamantyl acrylate (Meth)acrylates, 1-adamantyl methacrylates, and other pendant alicyclic functional groups. According to yet another embodiment, the pre-adhesive macromonomer may include an acrylic monomer. The component may contain terminal vinyl double bonds. According to yet another embodiment, the pre-adhesive malt is The chromomeric component may contain a terminal vinyl double bond. The macromonomer component is capable of being polymerized in a free radical polymerization process. It is possible.
[0033] According to a particular embodiment, the (meth)acrylic polymer component A has a low glass transition temperature According to yet another embodiment, the (meth)acrylic The polymer component A is determined based on the Tg of the homopolymer of the constituent monomers and their weight percentages. Each of these materials may have a specific glass transition temperature (Tg), as predicted by the Fox equation. For example, the (meth)acrylic polymer component A is heated to about 20° C. or less, for example, about 15° C. or less. or a glass transition temperature of about 10° C. or less, or about 5° C. or less, or about 0° C. or less The glass transition temperature of the (meth)acrylic polymer component A can be any one of the above. It will be understood that the (meth)acrylic poly It is further understood that the glass transition temperature of the polymer component A can be any value between any of the values recited above. It will be understood by others.
[0034] According to yet another embodiment, the adhesive composition comprises a specific content of (meth)acrylic polyvinyl chloride. For example, the adhesive composition may contain a (meth)acrylic polymer component A. The content of the adhesive composition is at least about 50.0% by weight, for example, at least about 50.0% by weight based on the total weight of the adhesive composition. at least about 52%, or at least about 55%, or at least about 57% by weight %, or at least about 60.0%, or at least about 62%, or at least at least about 65%, or at least about 67%, or at least about 70.0%, or at least about 72% by weight, or at least about 75% by weight, or even less According to yet another embodiment, the (meth)acrylic acid in the adhesive composition may be about 77% by weight. The content of the acrylic polymer component A is about 90.0% by weight based on the total weight of the adhesive composition. or less, for example, about 88% by weight or less, or about 85% by weight or less, or about 83% by weight or less; Or about 80% by weight or less, or even about 78% by weight or less in the adhesive composition. The content of the (meth)acrylic polymer component A is within a range between any of the minimum and maximum values described above. It will be understood that the range may be within the range. It is further noted that the content of component A may be any value between any of the minimum and maximum values mentioned above. It will be understood by others.
[0035] According to yet another embodiment, the (meth)acrylic polymer component A is The monomer component a may comprise the reaction product of a.1 and a2.
[0036] According to an embodiment, monomer component a1 may be an ethylenically unsaturated monomer. According to one embodiment, the ethylenically unsaturated monomer is an acid-containing (meth)acrylic monomer. (acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, etc.), hydroxyl-containing Acrylic monomer (2-hydroxyethyl (meth)acrylate), primary, Nitrogen-containing monomers with secondary or tertiary amino groups, as well as primary, secondary or may be selected from the group consisting of nitrogen-containing monomers having a tertiary amide group.
[0037] According to yet another embodiment, monomer component a2 may be an acrylate ester. According to yet another embodiment, the monomer component a2 has the formula C=C(R 2 )(COOR 1 )of wherein R1 is an alkyl group containing 1 to 24 carbon atoms. R2 is H or methyl.
[0038] According to yet another embodiment, the (meth)acrylic polymer component A has a specific content For example, the monomer component a1 in the (meth)acrylic polymer component A may be The content of component a1 is at least About 0.1% by weight, e.g., at least about 0.5% by weight, or at least about 1.0% by weight %, or at least about 1.5%, or at least about 2.0%, or at least or at least about 2.5%, or at least about 3.0%, or at least about 3.5% by weight %, or at least about 4.0%, or at least about 4.5%, or at least at least about 5.0% by weight, or at least about 5.5% by weight, or even at least about 6.0% by weight According to yet another embodiment, in the (meth)acrylic polymer component A, The content of the monomer component a1 is, relative to the total weight of the (meth)acrylic polymer component A, About 10% by weight or less, for example, about 9.5% by weight or less, or about 9.0% by weight or less, or 8.5% by weight or less, or about 8.0% by weight or less, or about 7.5% by weight or less, or about 7 .0% by weight or less, or about 6.5% by weight or less, or about 6.0% by weight or less, or about 5. 5% by weight or less, or about 5.0% by weight or less, or about 4.5% by weight or less, or about 4.0 % by weight or less, or about 3.5% by weight or less, or even about 3.0% by weight or less. The content of the monomer component a1 in the (meth)acrylic polymer component A is any minimum amount as described above. It will be understood that the range may be between the above and maximum values. The content of the monomer component a1 in the polymer component A may be any value between the minimum and maximum values described above. It will be further understood that the values may be any values.
[0039] According to yet another embodiment, the (meth)acrylic polymer component A has a specific content For example, the monomer component a2 in the (meth)acrylic polymer component A may be included. The content of the monomer component a2 is small relative to the total weight of the (meth)acrylic polymer component A. at least about 80% by weight, e.g., at least about 82% by weight, or at least about 85% by weight %, or at least about 87% by weight, or at least about 90% by weight, or at least about 92%, or at least about 95%, or at least about 97% by weight According to yet another embodiment, the monomer component a in the (meth)acrylic polymer component A The content of 2 is about 99.0% by weight based on the total weight of the (meth)acrylic polymer component A. The content of the monomer component a2 in the (meth)acrylic polymer component A can be: It will be understood that the range may be between any of the minimum and maximum values stated above. p) The content of the monomer component a2 in the acrylic polymer component A is the above-mentioned arbitrary minimum value. It will further be appreciated that the value may be any value between the maximum value.
[0040] According to one embodiment, the tackifier component is selected from the group consisting of C5, C9, C5 / C9, dicyclopentasiloxane, May include dienes, terpenes, or hydrogenated resins thereof, or combinations thereof. .
[0041] According to yet another embodiment, the adhesive composition comprises a specific content of a tackifier component. For example, the content of the tackifier component in the adhesive composition is based on the total weight of the adhesive composition. and at least 0.1% by weight, for example at least about 0.5% by weight, or at least about 1.0% by weight, or at least about 1.5% by weight, or at least about 2.0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight, or at least about 3.5% by weight, or at least about 4.0% by weight, or at least about 4.5% by weight; or at least about 5.0% by weight, or at least about 5.5% by weight, or at least about 6.0% by weight, or at least about 6.5% by weight, or at least about 7.0% by weight, or at least about 7.5% by weight, or at least about 8.0% by weight, or at least about 8.5% by weight, or at least about 9.0% by weight, or at least about 9.5% by weight; Or even at least about 10.0% by weight. The content of the tackifier component in the adhesive composition is about 30% by weight based on the total weight of the adhesive composition. % or less, for example, about 25% by weight or less, or about 20% by weight or less, or about 18% by weight or less or about 15% by weight or less, or about 13% by weight or less, or about 11% by weight or less. The content of the tackifier component in the adhesive composition may be any value between any of the minimum and maximum values set forth above. It will be understood that the content of the tackifier component in the adhesive composition may be within a range. It will be further understood that may be any value between any of the minimum and maximum values stated above. There will be.
[0042] With reference to the adhesive formed according to the embodiments described herein, the adhesive may include a particular According to an embodiment, the adhesive structure may include a graft copolymer. According to yet another embodiment, the graft copolymer of the adhesive construction may comprise a backbone According to yet another embodiment, the graft copolymer may include a graft side chain portion and a graft side chain portion. The main chain portion of the mer may include a (meth)acrylic polymer component A. According to the present invention, the graft side chain portion of the graft copolymer may include a macromonomer component. According to yet other embodiments, the adhesive construction may be formed via radiation initiated polymerization.
[0043] According to yet other embodiments, the adhesive formed according to the embodiments described herein comprises: It is applied as an adhesive layer on a substrate to form a tape. The base material of the tape is polytetrafluoroethylene, polyethylene terephthalate, polyethylene Styrene, polypropylene, polyvinyl chloride, polyimide, polyethylene naphthalate, Phenylene sulfide, ethylene tetrafluoroethylene, fluorinated ethylene propylene Any material selected from the group consisting of glass, aluminum foil, or a combination thereof. This may include fees.
[0044] With reference to the monolayer foam tape, the embodiments described herein generally refer to The invention may further relate to a single layer foam including an adhesive formed according to the described embodiments.
[0045] For illustrative purposes, FIG. 2 shows a monolayer foam formed according to an embodiment described herein. 2 includes an illustrative diagram showing the configuration of tape 200. As shown in FIG. 00 may include a foam core 210. The foam core 210 may include a hollow The microspheres 220 may include
[0046] According to certain embodiments, the single layer foam tape 200 may have a particular thickness. For example, , the single layer foam tape 200 may have a thickness of at least about 0.125 mm, e.g., at least about 0 0.13mm, or at least about 0.135mm, or at least about 0.14mm, or or at least about 0.145 mm, or at least about 0.15 mm, or at least About 0.155 mm, or at least about 0.16 mm, or at least about 0.165 m m, or at least about 0.17 mm, or at least about 0.175 mm, or further According to yet another embodiment, the single layer film may have a thickness of at least about 0.18 mm. The tape 200 may be about 0.25 mm or less, for example, about 0.245 mm or less, or about .24mm or less, or about 0.235mm or less, or about 0.23mm or less, or about 0 .225mm or less, or about 0.22mm or less, or about 0.215mm or less, or about 0.21mm or less, or about 0.205mm or less, or about 0.20mm or less, or about Thickness of 0.195 mm or less, or approximately 0.19 mm or less, or approximately 0.185 mm or less The thickness of the single layer foam tape 200 may range between any of the minimum and maximum values listed above. It will be understood that the thickness of the single layer foam tape 200 may be within the range described above. It will further be understood that the value may be any value between any of the minimum and maximum values.
[0047] According to an embodiment, the foam core 210 may have a particular thickness. The arm core 210 is at least about 0.125 mm, for example at least about 0.13 mm, Or at least about 0.135 mm, or at least about 0.14 mm, or at least At least about 0.145 mm, or at least about 0.15 mm, or at least about 0.155 mm, or at least about 0.16 mm, or at least about 0.165 mm, or less At least about 0.17 mm, or at least about 0.175 mm, or even at least According to yet another embodiment, the foam core 210 may have a thickness of about 0.18 mm. , about 0.25 mm or less, for example, about 0.245 mm or less, or about 0.24 mm or less, or about 0.235 mm or less, or about 0.23 mm or less, or about 0.225 mm or less, or about 0.22 mm or less, or about 0.215 mm or less, or about 0.21 mm or less, or about 0.205 mm or less, or about 0.20 mm or less, or about 0.195 mm or less , or about 0.19 mm or less, or about 0.185 mm or less. It is understood that the thickness of the core 210 can range between any of the minimum and maximum values stated above. The thickness of the foam core 210 may be any value between any of the minimum and maximum values set forth above. It will be further understood that the values may be any values.
[0048] According to certain embodiments, the hollow microspheres 220 can be of a particular material. The hollow microspheres 220 can be glass beads. The microspheres 220 may be polymerized microspheres. According to yet another embodiment, hollow microspheres 220 can be glass beads and polymeric microspheres.
[0049] With reference to the adhesive 230 formed according to the embodiments described herein, the adhesive 230 According to yet another embodiment, the adhesive 230 may include a specific adhesive composition. The adhesive composition includes a macromonomer component, which is partially dissolved before being added to the adhesive composition of the adhesive 230. The composition may comprise a (meth)acrylic polymer component A that is polymerized into the resin composition, and a tackifier component.
[0050] According to certain embodiments, the macromonomer component has a high glass transition temperature (Tg). According to yet another embodiment, the macromonomer component may be referred to as Based on the Tg of the homopolymer of the mer and its weight percentage, the Fox equation was used to predict For example, the macromonomer composition may have a specific glass transition temperature (Tg) as determined by the The heating time is at least about 40° C., e.g., at least about 45° C., or at least about 50° C. or at least about 55°C, or at least about 60°C, or at least about 65°C, or at least about 70° C., or at least about 75° C., or at least about 80° C., at least about 85° C., or at least about 95° C., or at least about 100° C., is at least about 105°C, or at least about 110°C, or at least about 115°C; or at least about 120° C., or at least about 125° C., or even at least about The glass transition temperature (Tg) of the macromonomer component may be 130° C. The glass transition temperature of the macromonomer component can be in the range between any of the values mentioned above. , it will be further understood that the value may be any value between any of the values stated above.
[0051] According to yet another embodiment, the macromonomer component may have a specific molecular weight. For example, the macromonomer component may have a molecular weight of at least about 1,000 g / mol, e.g., at least about 5,000 g / mol, or at least about 10,000 g / mol, or at least About 15,000 g / mol, or at least about 20,000 g / mol, or less Both have a molecular weight of about 25,000 g / mol, or at least about 30,000 g / mol. According to yet another embodiment, the macromonomer component may have a molecular weight of about 100,000 g / mol. mol or less, for example, about 75,000 g / mol or less, or about 50,000 g / mol or less The molecular weight of the macromonomer component may be less than or equal to any of the minimum and maximum values set forth above. It will be understood that the macromonomer component may be in the range between 0.1 and 1.0. It will be further understood that the minimum and maximum values may be any value between these minimum and maximum values.
[0052] According to yet another embodiment, the adhesive composition of the adhesive 230 has a particular content of macromolecules. For example, a macromonomer component in the adhesive composition of adhesive 230 may be included. The content of the adhesive 230 is at least about 2.0 wt. % based on the total weight of the adhesive composition. , for example, at least about 3.0% by weight, or at least about 4.0% by weight, or less At least about 5.0% by weight, or at least about 6.0% by weight, or at least about 7.0% by weight %, or at least about 8.0% by weight, or at least about 9.0% by weight, or less At least about 10.0% by weight, or at least about 12.5% by weight, or at least about 15. 0% by weight, or at least about 17.5% by weight, or at least about or even less According to yet another embodiment, the adhesive 230 may be about 20.0% by weight. The content of the macromonomer component in the composition is about 40.0% by weight based on the total weight of the adhesive composition. % by weight or less, for example, about 39% by weight or less, or about 38% by weight or less, or about 37% by weight or less or less than about 36% by weight, or less than about 35% by weight, or less than about 34% by weight, or about 33% by weight or less, or about 32% by weight or less, or about 31% by weight or less, or about 3 0% by weight or less, or about 29% by weight or less, or about 28% by weight or less, or about 27% by weight or less or less, or about 26% by weight or less, or even about 25% by weight or less. The content of the macromonomer component in the adhesive composition of No. 0 is between any of the minimum and maximum values described above. It will be appreciated that the amount of the macerated cellulose in the adhesive composition of adhesive 230 may be within a range. The content of the monomer component may be any value between any of the minimum and maximum values mentioned above. It will be further understood.
[0053] According to yet another embodiment, the macromonomer component is polymerized by reversible deactivation radical polymerization. can be advantageously synthesized through the use of controlled radical polymerization (RDRP) or controlled radical polymerization (CRP) techniques; Examples of these polymerization techniques include nitroxide mediated radical polymerization. (NMP), reversible addition-fragmentation chain transfer polymerization (RAFT), atom transfer radical polymerization (AT Catalytic Chain Transfer Polymerization (RP), and Cobalt-Mediated Catalytic Chain Transfer Polymerization (CCT). According to the form, the macromonomer component is cyclohexyl acrylate, cyclohexyl methacrylate, acrylate, isobornyl acrylate, isobornyl methacrylate, dicyclopentasiloxane Dicyclopentanyl acrylate, dicyclopentanyl methacrylate, 1-adamantyl acrylate (Meth)acrylates, 1-adamantyl methacrylates, and other pendant alicyclic functional groups. According to yet another embodiment, the pre-adhesive macromonomer may include an acrylic monomer. The component may contain terminal vinyl double bonds. According to yet another embodiment, the pre-adhesive malt is The chromomeric component may contain a terminal vinyl double bond. The macromonomer component is capable of being polymerized in a free radical polymerization process. It is possible.
[0054] According to a particular embodiment, the (meth)acrylic polymer component A has a low glass transition temperature According to yet another embodiment, the (meth)acrylic The polymer component A is determined based on the Tg of the homopolymer of the constituent monomers and their weight percentages. Each of these materials may have a specific glass transition temperature (Tg), as predicted by the Fox equation. For example, the (meth)acrylic polymer component A is heated to about 20° C. or less, for example, about 15° C. or less. or a glass transition temperature of about 10° C. or less, or about 5° C. or less, or about 0° C. or less The glass transition temperature of the (meth)acrylic polymer component A can be any one of the above. It will be understood that the (meth)acrylic poly It is further understood that the glass transition temperature of the polymer component A can be any value between any of the values recited above. It will be understood by others.
[0055] According to yet another embodiment, the adhesive composition of the adhesive 230 has a specific content of (meth) ) acrylic polymer component A. For example, the (meth)acrylic polymer component B in the adhesive composition of adhesive 230 may include p) The content of the acrylic polymer component A is based on the total weight of the adhesive composition of the adhesive 230. at least about 50.0% by weight, e.g., at least about 52% by weight, or at least about 55%, or at least about 57%, or at least about 60.0%, or at least about 62%, or at least about 65%, or at least about 67% by weight %, or at least about 70.0%, or at least about 72%, or less It may be at least about 75% by weight, or even at least about 77% by weight. According to the embodiment, the (meth)acrylic polymer component A in the adhesive composition of the adhesive 230 The content is about 90.0 wt % or less, for example, based on the total weight of the adhesive composition of the adhesive 230. For example, about 88% by weight or less, or about 85% by weight or less, or about 83% by weight or less, or about 8 0% or less, or even about 78% or less by weight. The content of the (meth)acrylic polymer component A in the composition is between any minimum and maximum values described above. It will be understood that the amount of (meth)acrylate in the adhesive composition of adhesive 230 may be in the range of 0.1 to 0.5%. ) The content of the acrylic polymer component A is any value between any minimum and maximum values mentioned above. It will be further appreciated that it may be possible.
[0056] According to yet another embodiment, the (meth)acrylic polymer component A is The monomer component a may comprise the reaction product of a.1 and a2.
[0057] According to an embodiment, monomer component a1 may be an ethylenically unsaturated monomer. According to one embodiment, the ethylenically unsaturated monomer is an acid-containing (meth)acrylic monomer. (acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, etc.), hydroxyl-containing Acrylic monomer (2-hydroxyethyl (meth)acrylate), primary, Nitrogen-containing monomers with secondary or tertiary amino groups, as well as primary, secondary or may be selected from the group consisting of nitrogen-containing monomers having a tertiary amide group.
[0058] According to yet another embodiment, monomer component a2 may be an acrylate ester. According to yet another embodiment, the monomer component a2 has the formula C=C(R 2 )(COOR 1 )of wherein R1 is an alkyl group containing 1 to 24 carbon atoms. R2 is H or methyl.
[0059] According to yet another embodiment, the (meth)acrylic polymer component A has a specific content For example, the monomer component a1 in the (meth)acrylic polymer component A may be The content of component a1 is at least About 0.1% by weight, e.g., at least about 0.5% by weight, or at least about 1.0% by weight %, or at least about 1.5%, or at least about 2.0%, or at least or at least about 2.5%, or at least about 3.0%, or at least about 3.5% by weight %, or at least about 4.0%, or at least about 4.5%, or at least at least about 5.0% by weight, or at least about 5.5% by weight, or even at least about 6.0% by weight According to yet another embodiment, in the (meth)acrylic polymer component A, The content of the monomer component a1 is, relative to the total weight of the (meth)acrylic polymer component A, About 10% by weight or less, for example, about 9.5% by weight or less, or about 9.0% by weight or less, or 8.5% by weight or less, or about 8.0% by weight or less, or about 7.5% by weight or less, or about 7 .0% by weight or less, or about 6.5% by weight or less, or about 6.0% by weight or less, or about 5. 5% by weight or less, or about 5.0% by weight or less, or about 4.5% by weight or less, or about 4.0 % by weight or less, or about 3.5% by weight or less, or even about 3.0% by weight or less. The content of the monomer component a1 in the (meth)acrylic polymer component A is any minimum amount as described above. It will be understood that the range may be between the above and maximum values. The content of the monomer component a1 in the polymer component A may be any value between the minimum and maximum values described above. It will be further understood that the values may be any values.
[0060] According to yet another embodiment, the (meth)acrylic polymer component A has a specific content For example, the monomer a2 in the (meth)acrylic polymer component A may be The content of component a2 is at least about 80% by weight, e.g., at least about 82% by weight, or at least about 85% by weight, At least about 87% by weight, or at least about 90% by weight, or at least about 92% by weight % by weight, or at least about 95% by weight, or at least about 97% by weight. According to another embodiment, the content of the monomer component a2 in the (meth)acrylic polymer component A is The content is about 99.0% by weight or less based on the total weight of the (meth)acrylic polymer component A. The content of the monomer component a2 in the (meth)acrylic polymer component A may be the same as that described above. It will be understood that the range may be between any minimum and maximum value. The content of the monomer component a2 in the acrylic polymer component A is within the range of any minimum and maximum values described above. It will be further understood that the value may be any value between
[0061] According to one embodiment, the tackifier component is selected from the group consisting of C5, C9, C5 / C9, dicyclopentasiloxane, May include dienes, terpenes, or hydrogenated resins thereof, or combinations thereof. .
[0062] According to yet another embodiment, the adhesive composition of the adhesive 230 has a specific content of tackifier. For example, the content of a tackifier component in the adhesive composition of the adhesive 230 may be is at least 0.1% by weight, for example, based on the total weight of the adhesive composition of the adhesive 230 At least about 0.5% by weight, or at least about 1.0% by weight, or at least about 1. 5% by weight, or at least about 2.0% by weight, or at least about 2.5% by weight, or At least about 3.0% by weight, or at least about 3.5% by weight, or at least about 4. 0% by weight, or at least about 4.5% by weight, or at least about 5.0% by weight, or At least about 5.5% by weight, or at least about 6.0% by weight, or at least about 6. 5% by weight, or at least about 7.0% by weight, or at least about 7.5% by weight, or At least about 8.0% by weight, or at least about 8.5% by weight, or at least about 9. 0% by weight, or at least about 9.5% by weight, or even at least about 10.0% by weight According to yet another embodiment, the tackifier in the adhesive composition of the adhesive 230 may be The content of the component is about 30% by weight or less, e.g., about 10% by weight or less, based on the total weight of the adhesive composition of the adhesive 230. For example, about 25% by weight or less, or about 20% by weight or less, or about 18% by weight or less, or about It may be 15% by weight or less, or about 13% by weight or less, or about 11% by weight or less. The content of the tackifier component in the adhesive composition of 230 is within the range of any minimum and maximum values described above. It will be appreciated that the tack of the adhesive 230 in the adhesive composition may be in the range between 0.1 and 0.25. The content of the additive component may be any value between any of the minimum and maximum values mentioned above. will be further understood.
[0063] With further reference to the adhesive 230 formed in accordance with embodiments described herein, the adhesive 230 may include a specific adhesive structure. According to an embodiment, the adhesion of the adhesive 230 The adhesive structure may include a graft copolymer. According to yet another embodiment, the adhesive structure The graft copolymer of the present invention may include a main chain portion and a grafted side chain portion. According to the embodiment, the main chain portion of the graft copolymer is a (meth)acrylic polymer component A According to yet another embodiment, the grafted side chain portion of the graft copolymer may comprise: According to yet another embodiment, the adhesive structure of the adhesive 230 may include a macromonomer component. The structures may be formed via radiation initiated polymerization.
[0064] Referring now to foam tapes, the embodiments described herein generally relate to foam At least a first adhesive layer of a first adhesive covering the core and the first surface of the foam core. The present invention relates to a foam tape comprising a first adhesive formed according to an embodiment described herein. Also included are adhesive compositions and adhesive constructions.
[0065] For illustrative purposes, FIG. 3 shows a foam tray formed according to an embodiment described herein. The foam tape 300 includes a foam core 310 and a and a first adhesive layer 340 of adhesive 350 covering the first surface 312 of the foam core 310. The foam core 310 may include hollow microspheres 320 within a foam material 330. do.
[0066] According to certain embodiments, the foam tape 300 may have a particular thickness. The foam tape 300 is at least about 0.10 mm, for example at least about 0.15 mm. , or at least about 0.2 mm, or at least about 0.25 mm, or at least about 0.3 mm, or at least about 0.35 mm, or at least about 0.4 mm, and may have a thickness of at least about 0.45 mm, or even at least about 0.5 mm. It is understood that the thickness of the foam tape 300 can range between any of the values recited above. The thickness of the foam tape 300 may be any value between any of the values recited above. It will be further appreciated that
[0067] According to an embodiment, the foam core 310 may have a particular thickness. The arm core 310 is at least about 0.125 mm, for example at least about 0.13 mm, Or at least about 0.135 mm, or at least about 0.14 mm, or at least At least about 0.145 mm, or at least about 0.15 mm, or at least about 0.155 mm, or at least about 0.16 mm, or at least about 0.165 mm, or less At least about 0.17 mm, or at least about 0.175 mm, or even at least According to yet another embodiment, the foam core 310 may have a thickness of about 0.18 mm. , about 0.25 mm or less, for example, about 0.245 mm or less, or about 0.24 mm or less, or about 0.235 mm or less, or about 0.23 mm or less, or about 0.225 mm or less, or about 0.22 mm or less, or about 0.215 mm or less, or about 0.21 mm or less, or about 0.205 mm or less, or about 0.20 mm or less, or about 0.195 mm or less , or about 0.19 mm or less, or about 0.185 mm or less. It is understood that the thickness of the core 310 can range between any of the minimum and maximum values stated above. The thickness of the foam core 310 may be any value between any of the minimum and maximum values set forth above. It will be further understood that the values may be any values.
[0068] According to certain embodiments, the hollow microspheres 320 can be of a particular material. The hollow microspheres 320 can be glass beads. The microspheres 320 may be polymerized microspheres. According to yet another embodiment, hollow microspheres 320 can be glass beads and polymeric microspheres.
[0069] According to yet other embodiments, the foam material 330 can be a specific material, such as According to yet another embodiment, the foam material 330 may be an acrylic material. The foam material 330 may be a polyurethane material. According to yet another embodiment, the foam material 330 may be a polyethylene material. The material 330 can be a PVC material. According to another embodiment, the foam material 330 is It may be an acrylic material, a polyurethane material, a polyethylene material, or a PVC material.
[0070] According to yet another embodiment, the foam material 330 may be an acrylic foam. According to yet another embodiment, the foam material 330 may be a polyurethane foam. .
[0071] According to an embodiment, the first adhesive layer 340 may have a particular thickness. The first adhesive layer 340 may be at least about 0.125 mm, e.g., at least about 0.13 mm. m, or at least about 0.135 mm, or at least about 0.14 mm, or less At least about 0.145 mm, or at least about 0.15 mm, or at least about 0.1 55 mm, or at least about 0.16 mm, or at least about 0.165 mm, and is at least about 0.17 mm, or at least about 0.175 mm, or even less According to yet another embodiment, the first adhesive layer 3 may have a thickness of about 0.18 mm. 40 is about 0.25 mm or less, for example, about 0.245 mm or less, or about 0.24 mm or less Below, or about 0.235 mm or less, or about 0.23 mm or less, or about 0.225 mm or less than about 0.22 mm, or less than about 0.215 mm, or less than about 0.21 mm or less than about 0.205 mm, or less than about 0.20 mm, or less than about 0.195 m The thickness may be about 0.19 mm or less, or about 0.185 mm or less. The thickness of the first adhesive layer 340 may be within a range between any of the minimum and maximum values stated above. It will be understood that the thickness of the first adhesive layer 340 may be within any of the minimum and maximum values set forth above. It will be further understood that the value may be any value between
[0072] The first adhesive 35 of the first adhesive layer 340 formed according to the embodiments described herein. 0, the first adhesive 350 may include a specific first adhesive composition. According to another embodiment, the adhesive composition of the first adhesive 350 comprises a first macromonomer component. component, a first (meth)acrylic polymer component A, and a first tackifier component. .
[0073] According to certain embodiments, the first macromonomer component has a high glass transition temperature (Tg) According to yet another embodiment, the first macromonomer component may be referred to as having is calculated based on the Tg of the homopolymer of the constituent monomers and their weight percentages. The first polymer may have a particular glass transition temperature (Tg) as predicted by the formula: The macromonomer component may be heated to at least about 40° C., for example at least about 45° C., or At least about 50° C., or at least about 55° C., or at least about 60° C., or at least at least about 65°C, or at least about 70°C, or at least about 75°C, or at least At least about 80°C, or at least about 85°C, or at least about 95°C, or at least At least about 100° C., or at least about 105° C., or at least about 110° C., or at least at least about 115°C, or at least about 120°C, or at least about 125°C, or It may further have a glass transition temperature (Tg) of at least about 130° C. The glass transition temperature of the first macromolecule may range between any of the values stated above. The glass transition temperature of the monomer component may be any value between any of the values recited above. will be further understood.
[0074] According to yet another embodiment, the first macromonomer component may have a specific molecular weight. For example, the first macromonomer component may have a molecular weight of at least about 1,000 g / mol, e.g., at least about 5,000 g / mol, or at least about 10,000 g / mol, or is at least about 15,000 g / mol, or at least about 20,000 g / mol; Or at least about 25,000 g / mol, or at least about 30,000 g / mol According to yet another embodiment, the first macromonomer component may have a molecular weight of about 100,000 g / mol or less, for example, about 75,000 g / mol or less, or about 50 The molecular weight of the first macromonomer component may be less than or equal to 1,000 g / mol. It will be understood that the range may be between any of the minimum and maximum values set forth above. The macromonomer component may be any value between any of the minimum and maximum values stated above. will be further understood.
[0075] According to yet another embodiment, the first adhesive composition of the first adhesive 350 comprises a specific For example, the first adhesive 350 may include a first macromonomer component. The content of the first macromonomer component in the adhesive composition is At least about 2.0% by weight, for example at least about 3.0% by weight, based on the total weight of the composition. %, or at least about 4.0% by weight, or at least about 5.0% by weight, or less At least about 6.0% by weight, or at least about 7.0% by weight, or at least about 8.0% by weight %, or at least about 9.0% by weight, or at least about 10.0% by weight, or less at least about 12.5%, or at least about 15.0%, or at least about 17. It may be .5% by weight, or at least about or even at least about 20.0% by weight. According to yet another embodiment, the first adhesive 350 includes a first macromolecule in the first adhesive composition. The content of the monomer component is about 40.0% by weight or less based on the total weight of the adhesive composition. For example, about 39% by weight or less, or about 38% by weight or less, or about 37% by weight or less, or about 36% by weight or less, or about 35% by weight or less, or about 34% by weight or less, or about 33% by weight or less % or less, or about 32% or less by weight, or about 31% or less by weight, or about 30% or less by weight, or about 29% by weight or less, or about 28% by weight or less, or about 27% by weight or less, or about The first adhesive 350 may be about 26% by weight or less, or even about 25% by weight or less. The content of the first macromonomer component in the adhesive composition is within any of the minimum and maximum values described above. It will be understood that the first adhesive 350 may be in the range between 0.1 mm and 0.2 mm. The content of the first macromonomer component in the agent composition is between any of the minimum and maximum values described above. It will be further understood that the value of may be any value.
[0076] According to yet another embodiment, the first macromonomer component comprises a reversible deactivation radical. These are advantageously synthesized through the use of controlled radical polymerization (RDRP) or controlled radical polymerization (CRP) techniques. Examples of these polymerization techniques include nitroxide mediated radical polymerization. Polymerization (NMP), Reversible Addition-Fragmentation Chain Transfer Polymerization (RAFT), Atom Transfer Radical Polymerization (ATRP), and cobalt-mediated catalytic chain transfer polymerization (CCT). According to this embodiment, the first macromonomer component is cyclohexyl acrylate, Isobornyl acrylate, Isobornyl methacrylate, Dicyclopentanyl acrylate, dicyclopentanyl methacrylate, 1-adamantine pendant alicyclic functional groups such as 1-adamantyl acrylate and 1-adamantyl methacrylate According to yet another embodiment, the pre-adhesive may include a (meth)acrylic monomer. The chromomeric component may contain a terminal vinyl double bond. The pre-adhesive macromonomer component may contain terminal vinyl double bonds. According to the embodiment, the first macromonomer component is polymerized in a free radical polymerization process. It may be possible to do so.
[0077] According to a particular embodiment, the first (meth)acrylic polymer component A has a low glass transition temperature. According to yet another embodiment, the first (metal) p) The acrylic polymer component A is the Tg and weight percent of the homopolymer of the constituent monomer. Based on the centimeter, the specific glass transition temperature (T For example, the first (meth)acrylic polymer component A may have a temperature of about 20° C. or less, For example, about 15° C. or less, about 10° C. or less, about 5° C. or less, or about 0° C. or less The glass transition temperature (Tg) of the first (meth)acrylic polymer component A may be It will be understood that the glass transition temperature can range between any of the values recited above. The glass transition temperature of the first (meth)acrylic polymer component A is any one of the above values. It will be further understood that the value may be any value between.
[0078] According to yet another embodiment, the first adhesive composition of the first adhesive 350 comprises a specific The first adhesive 35 may contain a sufficient amount of the first (meth)acrylic polymer component A. The content of the first (meth)acrylic polymer component A in the first adhesive composition of at least about 50.0 wt. %, based on the total weight of the first adhesive composition of the adhesive 350; For example, at least about 52% by weight, or at least about 55% by weight, or at least about 57% by weight, or at least about 60.0% by weight, or at least about 62% by weight, is at least about 65% by weight, or at least about 67% by weight, or at least about 70. 0% by weight, or at least about 72% by weight, or at least about 75% by weight, or According to yet another embodiment, the first adhesive 35 The content of the first (meth)acrylic polymer component A in the first adhesive composition of About 90.0% by weight or less, for example, based on the total weight of the first adhesive composition of the adhesive 350 , about 88% by weight or less, or about 85% by weight or less, or about 83% by weight or less, or about 80% by weight or less % or less, or even about 78% or less by weight. The content of the first (meth)acrylic polymer component A in the adhesive composition is any minimum amount as described above. It will be understood that the thickness of the first adhesive 350 may be within a range between the above and maximum values. The content of the first (meth)acrylic polymer component A in the first adhesive composition may be any of the above. It will be further understood that the minimum and maximum values may be any value between these minimum and maximum values.
[0079] According to yet another embodiment, the first (meth)acrylic polymer component A is The first monomer component a1 may comprise the reaction product of a first monomer component a2.
[0080] According to one embodiment, the first monomer component a1 is an ethylenically unsaturated monomer. According to one embodiment, the ethylenically unsaturated monomer is an acid-containing (meth)acrylic monomer. Monomers (acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, etc.), hydrochloric acid, (meth)acrylic monomer containing 2-hydroxyethyl (meth)acrylate, Nitrogen-containing monomers with primary, secondary, or tertiary amino groups, and primary, secondary or a nitrogen-containing monomer having a tertiary amide group.
[0081] According to yet another embodiment, the first monomer component a2 is an acrylic ester. According to yet another embodiment, the first monomer component a2 has the formula C=C(R 2 )(C OOR 1 wherein R1 is an acrylic acid ester having 1 to 24 carbon atoms. and R2 is H or methyl.
[0082] According to yet another embodiment, the first (meth)acrylic polymer component A comprises a specific For example, the first (meth)acrylic polymer may contain a first monomer component a1. The content of the first monomer component a1 in the component A is At least about 0.1% by weight, for example at least about 0.5% by weight, based on the total weight of A; or at least about 1.0% by weight, or at least about 1.5% by weight, or at least about 2.0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight; or at least about 3.5% by weight, or at least about 4.0% by weight, or at least about 4.5% by weight, or at least about 5.0% by weight, or at least about 5.5% by weight; Or even at least about 6.0% by weight. According to yet another embodiment, the first The content of the first monomer component a1 in the (meth)acrylic polymer component A is the first ( About 10% by weight or less, for example about 9. 5% by weight or less, or about 9.0% by weight or less, or about 8.5% by weight or less, or about 8.0 % by weight or less, or about 7.5% by weight or less, or about 7.0% by weight or less, or about 6.5% by weight or less % by weight or less, or about 6.0% by weight or less, or about 5.5% by weight or less, or about 5.0% by weight or less % or less, or about 4.5% by weight or less, or about 4.0% by weight or less, or about 3.5% by weight The first (meth)acrylic polymer may be about 3.0% by weight or less, or even about 3.0% by weight or less. The content of the first monomer component a1 in the component A is within a range between any of the minimum and maximum values mentioned above. It will be understood that the range may be within the range. The content of the first monomer component a1 may be any value between any minimum and maximum values mentioned above. It will be further understood that this is possible.
[0083] According to yet another embodiment, the first (meth)acrylic polymer component A comprises a specific For example, the first (meth)acrylic polymer may contain a first monomer component a2. The content of the first monomer component a2 in the component A is At least about 80% by weight, for example at least about 82% by weight, based on the total weight of A; At least about 85% by weight, or at least about 87% by weight, or at least about 90% by weight %, or at least about 92% by weight, or at least about 95% by weight, or at least According to yet another embodiment, the first (meth)acrylic polymer may be about 97% by weight. The content of the first monomer component a2 in the polymer component A is - It can be about 99.0% by weight or less based on the total weight of component A. The first (meth)acrylic The content of the first monomer component a2 in the system polymer component A is within the above-mentioned arbitrary minimum and maximum values. It will be understood that the range of the first (meth)acrylic polymer may be between 1 and 2. The content of the first monomer component a2 in the component A is between any of the minimum and maximum values mentioned above. It will further be appreciated that it can be any value.
[0084] According to one embodiment, the first tackifier component is a C5, C9, C5 / C9, dicyclo pentadiene, terpene, or hydrogenated resins thereof, or combinations thereof. It can be seen.
[0085] According to yet another embodiment, the first adhesive composition of the first adhesive 350 comprises a specific For example, the first adhesive composition of the first adhesive 350 may include a first tackifier component. The content of the first tackifier component in the first adhesive composition of the first adhesive 350 is At least 0.1% by weight, for example at least about 0.5% by weight, based on the total weight; or At least about 1.0% by weight, or at least about 1.5% by weight, or at least about 2. 0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight, or At least about 3.5% by weight, or at least about 4.0% by weight, or at least about 4. 5% by weight, or at least about 5.0% by weight, or at least about 5.5% by weight, or At least about 6.0% by weight, or at least about 6.5% by weight, or at least about 7. 0% by weight, or at least about 7.5% by weight, or at least about 8.0% by weight, or At least about 8.5% by weight, or at least about 9.0% by weight, or at least about 9. 5% by weight, or even at least about 10.0% by weight. According to this, the content of the first tackifier component in the first adhesive composition of the first adhesive 350 is , about 30% by weight or less, for example, based on the total weight of the first adhesive composition of the first adhesive 350 For example, about 25% by weight or less, or about 20% by weight or less, or about 18% by weight or less, or about 1 It may be 5% by weight or less, or about 13% by weight or less, or about 11% by weight or less. The content of the first imparting agent component in the first adhesive composition of the adhesive 350 is any minimum value as described above. It will be appreciated that the thickness of the first adhesive 350 may be in the range between 0.1 and 0.2 mm. The content of the first tackifier component in the adhesive composition of 1 may be any minimum or maximum value as described above. It will be further understood that the value may be any value between
[0086] With further reference to the first adhesive 350 formed according to embodiments described herein, The first adhesive 350 may include a specific first adhesive structure. According to an embodiment, The first adhesive structure of the first adhesive 350 may include a graft copolymer. According to this embodiment, the graft copolymer of the first adhesive structure comprises a main chain portion and a graft copolymer. According to yet another embodiment, the main chain portion of the graft copolymer may include a graft side chain portion. may comprise a first (meth)acrylic polymer component A. According to yet another embodiment, The graft side chain portion of the graft copolymer may include the first macromonomer component. According to yet another embodiment, the first adhesive structure of the first adhesive 350 is a radiation-initiated polymer. The above-mentioned structure may be formed through bonding.
[0087] For illustrative purposes, FIG. 4 shows a foam tray formed according to an embodiment described herein. The foam tape 400 includes a foam core 410, a foam tape 410b, and a foam tape 410c. A first adhesive layer 440 of a first adhesive 450 covering the first surface 412 of the foam core 410. , and a second adhesive 470 covering the second surface 414 of the foam core 410. The foam core 410 may include a layer of hollow microspheres 460 within the foam material 430. It may include 20.
[0088] The foam tape 400 has been described with reference to the foam tape 400 shown in FIG. 0 and all components are as described herein with reference to the corresponding components shown in FIG. Specifically, the foam tape 400 shown in FIG. The adhesive layer 410, the hollow microspheres 420, the foam material 430, the first adhesive layer 440, and the second adhesive layer 440. The properties of the adhesive 450 of FIG. 1 are shown in FIG. 0, hollow microspheres 320, foam material 330, first adhesive layer 340, and first adhesive layer 340. The adhesive 350 may have any of the corresponding characteristics described herein with reference to the adhesive 350.
[0089] According to an embodiment, the second adhesive layer 460 may have a particular thickness. The second adhesive layer 460 is at least about 0.125 mm, for example at least about 0.13 mm. m, or at least about 0.135 mm, or at least about 0.14 mm, or less At least about 0.145 mm, or at least about 0.15 mm, or at least about 0.1 55 mm, or at least about 0.16 mm, or at least about 0.165 mm, and is at least about 0.17 mm, or at least about 0.175 mm, or even less According to yet another embodiment, the second adhesive layer 3 may have a thickness of about 0.18 mm. 60 is about 0.25 mm or less, for example, about 0.245 mm or less, or about 0.24 mm or less Below, or about 0.235 mm or less, or about 0.23 mm or less, or about 0.225 mm or less than about 0.22 mm, or less than about 0.215 mm, or less than about 0.21 mm or less than about 0.205 mm, or less than about 0.20 mm, or less than about 0.195 m The thickness may be about 0.19 mm or less, or about 0.185 mm or less. The thickness of the second adhesive layer 460 may be within a range between any of the minimum and maximum values mentioned above. It will be understood that the thickness of the second adhesive layer 460 may be within any of the minimum and maximum values set forth above. It will be further understood that the value may be any value between
[0090] The second adhesive 47 of the second adhesive layer 460 formed according to the embodiments described herein. 0, the second adhesive 470 may include a specific second adhesive composition. According to another embodiment, the second adhesive composition of the second adhesive 470 comprises a second macromonomer. A (meth)acrylic polymer component A, a second (meth)acrylic polymer component B, and a second tackifier component It can be seen.
[0091] According to certain embodiments, the second macromonomer component has a high glass transition temperature (Tg) According to yet another embodiment, the second macromonomer component may be referred to as having is calculated based on the Tg of the homopolymer of the constituent monomers and their weight percentages. The polymer may have a particular glass transition temperature (Tg) as predicted by the formula: The macromonomer component may be heated to at least about 40° C., for example at least about 45° C., or At least about 50° C., or at least about 55° C., or at least about 60° C., or at least at least about 65° C., or at least about 70° C., or at least about 75° C., or even At least about 80° C., or at least about 85° C., or at least about 95° C., or at least about at least about 100° C., or at least about 105° C., or at least about 110° C., is at least about 115°C, or at least about 120°C, or at least about 125°C; Or may further have a glass transition temperature (Tg) of at least about 130° C. The glass transition temperature of the monomer component can range between any of the values recited above. The glass transition temperature of the macromonomer component can be any value between any of the values stated above. It will be further understood.
[0092] According to yet another embodiment, the second macromonomer component may have a specific molecular weight. For example, the second macromonomer component may have a molecular weight of at least about 1,000 g / mol, e.g. at least about 5,000 g / mol, or at least about 10,000 g / mol, or is at least about 15,000 g / mol, or at least about 20,000 g / mol; Or at least about 25,000 g / mol, or at least about 30,000 g / mol According to yet another embodiment, the second macromonomer component may have a molecular weight of about 100,000 g / mol or less, for example, about 75,000 g / mol or less, or about 50 The molecular weight of the second macromonomer component may be less than or equal to 1,000 g / mol. It will be understood that the range may be between any of the minimum and maximum values set forth above. The macromonomer component may be any value between any of the minimum and maximum values stated above. will be further understood.
[0093] According to yet another embodiment, the second adhesive composition of the second adhesive 470 may include a specific For example, the second adhesive 470 may include a second macromonomer component. The content of the second macromonomer component in the adhesive composition is At least about 2.0% by weight, for example at least about 3.0% by weight, based on the total weight of the composition. %, or at least about 4.0% by weight, or at least about 5.0% by weight, or less At least about 6.0% by weight, or at least about 7.0% by weight, or at least about 8.0% by weight %, or at least about 9.0% by weight, or at least about 10.0% by weight, or less at least about 12.5%, or at least about 15.0%, or at least about 17. It may be .5% by weight, or at least about or even at least about 20.0% by weight. According to yet another embodiment, the second adhesive 470 includes a second macromolecule in a second adhesive composition. The content of the monomer component is about 40.0% by weight or less based on the total weight of the adhesive composition. For example, about 39% by weight or less, or about 38% by weight or less, or about 37% by weight or less, or about 36% by weight or less, or about 35% by weight or less, or about 34% by weight or less, or about 33% by weight or less % or less, or about 32% or less by weight, or about 31% or less by weight, or about 30% or less by weight, or about 29% by weight or less, or about 28% by weight or less, or about 27% by weight or less, or about The second adhesive 470 may be about 26% by weight or less, or even about 25% by weight or less. The content of the second macromonomer component in the adhesive composition is within any minimum and maximum values described above. It will be understood that the second adhesive 470 may be in the range between 0.1 and 0.25 mm. The content of the second macromonomer component in the agent composition may be between any of the minimum and maximum values described above. It will be further understood that the value of may be any value.
[0094] According to yet another embodiment, the second macromonomer component comprises a reversible deactivation radical. These are advantageously synthesized through the use of controlled radical polymerization (RDRP) or controlled radical polymerization (CRP) techniques. Examples of these polymerization techniques include nitroxide mediated radical polymerization. Polymerization (NMP), Reversible Addition-Fragmentation Chain Transfer Polymerization (RAFT), Atom Transfer Radical Polymerization (ATRP), and cobalt-mediated catalytic chain transfer polymerization (CCT). According to this embodiment, the second macromonomer component is cyclohexyl acrylate, Isobornyl acrylate, Isobornyl methacrylate, Dicyclopentanyl acrylate, dicyclopentanyl methacrylate, 1-adamantine pendant alicyclic functional groups such as 1-adamantyl acrylate and 1-adamantyl methacrylate According to yet another embodiment, the pre-adhesive may include a (meth)acrylic monomer. The chromomeric component may contain a terminal vinyl double bond. The pre-adhesive macromonomer component may contain terminal vinyl double bonds. According to the embodiment, the second macromonomer component is polymerized in a free radical polymerization process. It may be possible to do so.
[0095] According to a particular embodiment, the second (meth)acrylic polymer component A has a low glass transition temperature. According to yet another embodiment, the second (metal) p) The acrylic polymer component A is the Tg and weight percent of the homopolymer of the constituent monomer. Based on the centimeter, the specific glass transition temperature (T For example, the second (meth)acrylic polymer component A may have a temperature of about 20° C. or less. For example, about 15° C. or less, about 10° C. or less, about 5° C. or less, or about 0° C. or less The glass transition temperature (Tg) of the second (meth)acrylic polymer component A may be It will be understood that the glass transition temperature can range between any of the values recited above. The glass transition temperature of the second (meth)acrylic polymer component A is any one of the above values. It will be further understood that the value may be any value between.
[0096] According to yet another embodiment, the second adhesive composition of the second adhesive 470 may include a specific A second adhesive 47 may contain a substantial amount of a second (meth)acrylic polymer component A. The content of the second (meth)acrylic polymer component A in the second adhesive composition of at least about 50.0 wt. %, based on the total weight of the second adhesive composition of the adhesive 470; For example, at least about 52% by weight, or at least about 55% by weight, or at least about 57% by weight, or at least about 60.0% by weight, or at least about 62% by weight, is at least about 65% by weight, or at least about 67% by weight, or at least about 70. 0% by weight, or at least about 72% by weight, or at least about 75% by weight, or According to yet another embodiment, the second adhesive 47 may be at least about 77% by weight. The content of the second (meth)acrylic polymer component A in the second adhesive composition of About 90.0 wt. % or less, for example, based on the total weight of the second adhesive composition of the adhesive 470 , about 88% by weight or less, or about 85% by weight or less, or about 83% by weight or less, or about 80% by weight or less % or less, or even about 78% or less by weight. The content of the second (meth)acrylic polymer component A in the adhesive composition may be any minimum amount as described above. It will be understood that the thickness of the second adhesive 470 may be within a range between the above and maximum values. The content of the second (meth)acrylic polymer component A in the second adhesive composition may be any of the above. It will be further understood that the minimum and maximum values may be any value between these minimum and maximum values.
[0097] According to yet another embodiment, the second (meth)acrylic polymer component A is The monomer component a1 may comprise the reaction product of a first monomer component a1 and a second monomer component a2.
[0098] According to one embodiment, the second monomer component a1 is an ethylenically unsaturated monomer. According to one embodiment, the ethylenically unsaturated monomer is an acid-containing (meth)acrylic monomer. Monomers (acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, etc.), hydrochloric acid, (meth)acrylic monomer containing 2-hydroxyethyl (meth)acrylate, Nitrogen-containing monomers with primary, secondary, or tertiary amino groups, and primary, secondary or a nitrogen-containing monomer having a tertiary amide group.
[0099] According to yet another embodiment, the second monomer component a2 is an acrylic ester. According to yet another embodiment, the second monomer component a2 has the formula C=C(R 2 )(C OOR 1 wherein R1 is an acrylic acid ester having 1 to 24 carbon atoms. and R2 is H or methyl.
[0100] According to yet another embodiment, the second (meth)acrylic polymer component A comprises a specific A second monomer component a1 may be included in the composition. For example, the second (meth)acrylic polymer may include The content of the second monomer component a1 in the component A is At least about 0.1% by weight, for example at least about 0.5% by weight, based on the total weight of A; or at least about 1.0% by weight, or at least about 1.5% by weight, or at least about 2.0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight; or at least about 3.5% by weight, or at least about 4.0% by weight, or at least about 4.5% by weight, or at least about 5.0% by weight, or at least about 5.5% by weight; Or even at least about 6.0% by weight. According to yet another embodiment, the second The content of the second monomer component a1 in the (meth)acrylic polymer component A is the second ( About 10% by weight or less, for example about 9. 5% by weight or less, or about 9.0% by weight or less, or about 8.5% by weight or less, or about 8.0 % by weight or less, or about 7.5% by weight or less, or about 7.0% by weight or less, or about 6.5% by weight or less % by weight or less, or about 6.0% by weight or less, or about 5.5% by weight or less, or about 5.0% by weight or less % or less, or about 4.5% by weight or less, or about 4.0% by weight or less, or about 3.5% by weight The second (meth)acrylic polymer may be about 3.0% by weight or less, or even about 3.0% by weight or less. The content of the second monomer component a1 in the component A may be within a range between any of the minimum and maximum values mentioned above. It will be understood that the range may be within the range. The content of the second monomer component a1 may be any value between any minimum and maximum values mentioned above. It will be further understood that this is possible.
[0101] According to yet another embodiment, the second (meth)acrylic polymer component A comprises a specific A second monomer component a2 may be included in the copolymer. For example, a second (meth)acrylic polymer The content of the second monomer component a2 in the component A is At least about 80% by weight, for example at least about 82% by weight, based on the total weight of A; At least about 85% by weight, or at least about 87% by weight, or at least about 90% by weight %, or at least about 92% by weight, or at least about 95% by weight, or at least According to yet another embodiment, the second (meth)acrylic polymer may be about 97% by weight. The content of the second monomer component a2 in the polymer component A is - It can be about 99.0% by weight or less based on the total weight of component A. The content of the second monomer component a2 in the system polymer component A is within the above-mentioned arbitrary minimum and maximum values. It will be understood that the second (meth)acrylic polymer may be in the range between The content of the second monomer component a2 in the component A is between any of the minimum and maximum values mentioned above. It will further be appreciated that it can be any value.
[0102] According to one embodiment, the second tackifier component is a C5, C9, C5 / C9, dicyclo pentadiene, terpene, or hydrogenated resins thereof, or combinations thereof. It can be seen.
[0103] According to yet another embodiment, the second adhesive composition of the second adhesive 470 may include a specific For example, the second adhesive composition of the second adhesive 470 may include a second tackifier component. The content of the second tackifier component in the second adhesive composition of the second adhesive 470 is At least 0.1% by weight, for example at least about 0.5% by weight, based on the total weight; or At least about 1.0% by weight, or at least about 1.5% by weight, or at least about 2. 0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight, or At least about 3.5% by weight, or at least about 4.0% by weight, or at least about 4. 5% by weight, or at least about 5.0% by weight, or at least about 5.5% by weight, or At least about 6.0% by weight, or at least about 6.5% by weight, or at least about 7. 0% by weight, or at least about 7.5% by weight, or at least about 8.0% by weight, or At least about 8.5% by weight, or at least about 9.0% by weight, or at least about 9. 5% by weight, or even at least about 10.0% by weight. According to this, the content of the second tackifier component in the second adhesive composition of the second adhesive 470 is , about 30% by weight or less, based on the total weight of the second adhesive composition of the second adhesive 470, for example For example, about 25% by weight or less, or about 20% by weight or less, or about 18% by weight or less, or about 1 It may be 5% by weight or less, or about 13% by weight or less, or about 11% by weight or less. The content of the second tackifier component in the second adhesive composition of the adhesive 470 may be any maximum amount of the above. It will be understood that the thickness of the second adhesive 470 may be within a range between the minimum and maximum values. The content of the second tackifier component in the second adhesive composition may be within any minimum and maximum values described above. It will be further understood that the value may be any value between
[0104] With further reference to the second adhesive 470 formed according to embodiments described herein, The second adhesive 470 may include a specific second adhesive structure. According to an embodiment, The second adhesive structure of the second adhesive 470 may include a graft copolymer. According to this embodiment, the graft copolymer of the second adhesive structure comprises a main chain portion and a graft copolymer. According to yet another embodiment, the main chain portion of the graft copolymer may include a graft side chain portion. may contain a second (meth)acrylic polymer component A. According to yet another embodiment, Alternatively, the grafted side chain portion of the graft copolymer may include a second macromonomer component. According to yet another embodiment, the second adhesive structure of the second adhesive 470 is a radiation-initiated polymer. The above-mentioned structure may be formed through bonding.
[0105] Many different aspects and embodiments are possible. After reading this specification, those skilled in the art will be able to easily understand these aspects and implementations. It will be understood that the embodiments are illustrative only and do not limit the scope of the present invention. Any one or more of the embodiments listed below may be followed.
[0106] Embodiment 1. An adhesive comprising an adhesive structure and an adhesive composition, the adhesive structure comprising and a graft copolymer, the adhesive composition comprising at least Each of the macromonomer components is about 1% by weight and about 40% by weight or less of the total adhesive composition. whereas at least about 50% by weight and no more than about 98% by weight of a (meth)acrylic polymer Component A and at least about 0.1 wt. % and about 30 wt. % based on the total weight of the adhesive composition % or less of a tackifier component, and the macromonomer component is at least 1000 g / m ol, and the macromonomer component has a glass transition temperature of at least about 40° C. and (meth)acrylic polymer component A has a glass transition temperature (T g).
[0107] Embodiment 2. The graft copolymer of the adhesive structure comprises a main chain portion and a graft side chain portion. The main chain portion contains a (meth)acrylic polymer component A, and the graft side chain portion contains 2. The adhesive of embodiment 1, comprising a macromonomer component.
[0108] Embodiment 3. The graft copolymer of the adhesive construction is formed via radiation initiated polymerization. 3. The adhesive of embodiment 1 or 2.
[0109] Embodiment 4. The (meth)acrylic polymer component A is a (meth)acrylic polymer component At least about 0.1% by weight and not more than about 10% by weight of monomer components, based on the total weight of A a1, which comprises an ethylenically unsaturated functional monomer having a pendant hydrogen bonding group; At least Between about 80% by weight and about 99% by weight or less of monomer component a2, and a reaction product of a polymerizable material comprising a monomer component a2, 3. The adhesive of claim 1 or 2.
[0110] Embodiment 5. The monomer component a1 is an acid-containing (meth)acrylic monomer (acrylic acid, meth ... Acrylic acid, 2-carboxyethyl acrylate, etc.), hydroxy-containing (meth)acrylic Monomer (2-hydroxyethyl (meth)acrylate), primary, secondary, or primary Nitrogen-containing monomers with a tertiary amino group and a primary, secondary, or tertiary amide group an ethylenically unsaturated functional monomer selected from the group consisting of nitrogen-containing monomers having the formula: 5. The adhesive of embodiment 4, comprising:
[0111] Embodiment 6. The monomer component a2 is an acrylic acid ester of the formula C=C(R2)(COOR1). R1 is an alkyl group containing 1 to 24 carbon atoms and R2 is H or methyl.
[0112] Embodiment 7. The macromonomer component is a (meth)acrylic polymer having a pendant alicyclic functional group. and the macromonomer component is polymerized in a free radical polymerization process. 3. The adhesive of embodiment 1 or 2, which can be
[0113] Embodiment 8. The tackifier component is a C5, C9, C5 / C9, dicyclopentadiene , terpenes, or hydrogenated resins thereof, or combinations thereof. 3. The adhesive according to claim 1 or 2.
[0114] Embodiment 9. The adhesive composition has a viscosity of at least about 2.0 times the total weight of the adhesive composition. %, at least about 3.0% by weight, or at least about 4.0% by weight, or at least about 5.0% by weight, or at least about 6.0% by weight, or at least about 7.0% by weight, or at least about 8.0% by weight, or at least about 9.0% by weight, or at least About 10.0% by weight, or at least about 12.5% by weight, or at least about 15.0% by weight %, or at least about 17.5% by weight, or at least about 20 The adhesive of embodiment 1 or 2, comprising .0 wt.% of the macromonomer component.
[0115] Embodiment 10. The adhesive composition comprises about 40% by weight or less of the total weight of the adhesive composition. About 39% by weight or less, or about 38% by weight or less, or about 37% by weight or less, or about 36% by weight or less % by weight or less, or about 35% by weight or less, or about 34% by weight or less, or about 33% by weight or less or about 32% by weight or less, or about 31% by weight or less, or about 30% by weight or less, or About 29% by weight or less, or about 28% by weight or less, or about 27% by weight or less, or about 26% by weight or less % or less, or about 25% or less by weight of the macromonomer component. The adhesive described.
[0116] Embodiment 11. The adhesive composition comprises at least about 50% by weight, at least about 52% by weight, Or at least about 55% by weight, or at least about 57% by weight, or at least about 6 0.0% by weight, or at least about 62% by weight, or at least about 65% by weight, or At least about 67% by weight, or at least about 70.0% by weight, or at least about 72 %, or at least about 75%, or at least about 77%, or less by weight The composition according to any one of the first and second embodiments, each of which contains about 80% by weight of the (meth)acrylic polymer component A. Adhesive included.
[0117] Embodiment 12. The adhesive composition comprises about 90% by weight or less, about 88% by weight or less, or about 85% by weight or less. % by weight or less, or 83% by weight or less, or 80% by weight or less, or 78% by weight or less (Me The adhesive according to embodiment 1 or 2, comprising an acrylic polymer component A.
[0118] Embodiment 13. The adhesive composition comprises at least about 0.1% by weight of the total adhesive composition. %, at least about 0.5%, or at least about 1.0%, or at least or at least about 1.5%, or at least about 2.0%, or at least about 2.5% by weight %, or at least about 3.0%, or at least about 3.5%, or at least or at least about 4.0% by weight, or at least about 4.5% by weight, or at least about 5.0% by weight %, or at least about 5.5%, or at least about 6.0%, or at least or at least about 6.5%, or at least about 7.0%, or at least about 7.5% by weight %, or at least about 8.0%, or at least about 8.5%, or at least or at least about 9.0%, or at least about 9.5%, or at least about 10% by weight The adhesive of embodiment 1 or 2 comprising a tackifier component.
[0119] Embodiment 14. The adhesive composition comprises about 30% by weight or less of the total weight of the adhesive composition. About 28% by weight or less, or 25% by weight or less, or 23% by weight or less, or 20% by weight or less or less than 18% by weight, or less than 15% by weight, or less than 13% by weight, or less than 11% by weight 3. The adhesive of embodiment 1 or 2, comprising up to 5% by weight of a tackifier component.
[0120] Embodiment 15. The (meth)acrylic polymer component A is a (meth)acrylic polymer component at least about 0.1% by weight, at least about 0.5% by weight, based on the total weight of part A; or At least about 1.0% by weight, or at least about 1.5% by weight, or at least about 2. 0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight, or At least about 3.5% by weight, or at least about 4.0% by weight, or at least about 4. 5% by weight, or at least about 5.0% by weight, or at least about 5.5% by weight, or 1 or 2, further comprising at least about 6.0% by weight of a (meth)acrylic polymer component A. 2. The adhesive described in 2.
[0121] Embodiment 16: (Meth)acrylic polymer component A is a (meth)acrylic polymer component About 10.0% by weight or less, about 9.5% by weight or less, or about 9.0% by weight or less, based on the total weight of component A % by weight or less, or about 8.5% by weight or less, or about 8.0% by weight or less, or about 7.5% by weight or less % or less, or about 7.0% by weight or less, or about 6.5% by weight or less, or about 6.0% by weight or less or less than about 5.5% by weight, or less than about 5.0% by weight, or less than about 4.5% by weight or less than about 4.0% by weight, or less than about 3.5% by weight, or less than about 3.0% by weight 3. The adhesive of embodiment 1 or 2, comprising a monomer component a1 of
[0122] Embodiment 17. The (meth)acrylic polymer component A is a (meth)acrylic polymer component At least about 80% by weight, at least about 82% by weight, or less, based on the total weight of component A at least about 85%, or at least about 87%, or at least about 90%, Or at least about 92% by weight, or at least about 95% by weight, or at least about 9 3. The adhesive according to embodiment 1 or 2, comprising 7 wt.-% of monomer component a2.
[0123] Embodiment 18. The (meth)acrylic polymer component A comprises about 99% by weight or less. 3. The adhesive of embodiment 1 or 2.
[0124] Embodiment 19. A method of forming an adhesive, the method comprising providing a pre-adhesive mixture. and wherein the pre-adhesive mixture comprises at least about 1% by weight and up to about 40% by weight of a pre-adhesive macromonomer component, having a molecular weight of about 1000 g / mol and a glass transition temperature of at least about 40° C. , based on the total weight of the pre-adhesive macromonomer component and the pre-adhesive mixture, at least about 50% by weight and up to about 98% by weight of pre-adhesive (meth)acrylic polymer component A. and a pre-adhesive (meth)acrylic based having a glass transition temperature (Tg) of about 20°C or less. Polymer component A and at least about 0.1% by weight based on the total weight of the pre-adhesive mixture and about 30% by weight or less of a pre-adhesive tackifier component; mixing the pre-adhesive mixture and polymerizing the pre-adhesive mixture to form an adhesive. The adhesive comprises an adhesive structure and an adhesive composition, the adhesive structure comprising: and polymerizing the copolymer.
[0125] Embodiment 20. Pre-adhesive (meth)acrylic polymer component A is a pre-adhesive (meth)acrylic polymer component B. At least about 0.1% by weight and about 10% by weight based on the total weight of the acrylic polymer component A % or less of pre-adhesive monomer component a1, which is an ethylenediamine having pendant hydrogen bonding groups. a1, a monomer component of the pre-adhesive, including a cyclic unsaturated functional monomer, and the total weight of the pre-adhesive at least about 80% by weight and up to about 99% by weight of pre-adhesive monomer component a 2, and a pre-adhesive monomer component a2, which comprises an ethylenically unsaturated monomer. 20. The method of embodiment 19, comprising the reaction product of a polymerizable material.
[0126] Embodiment 21. The pre-adhesive monomer component a1 is an acid-containing (meth)acrylic monomer (a Acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, etc.), hydroxy-containing ( Meth)acrylic monomer (2-hydroxyethyl (meth)acrylate), primary, secondary Nitrogen-containing monomers having primary, secondary or tertiary amino groups, and primary, secondary or tertiary amino groups. a nitrogen-containing monomer having an ethylenically unsaturated group selected from the group consisting of a nitrogen-containing monomer having a tertiary amide group; 21. The method of embodiment 20, comprising a functional monomer.
[0127] Embodiment 22. The pre-adhesive monomer component a2 has the formula C=C(R2)(COOR1). wherein R1 is an alkyl group containing 1 to 24 carbon atoms. and R2 is H or methyl.
[0128] Embodiment 23. The pre-adhesive macromonomer component has pendant alicyclic functional groups ( The pre-adhesive macromonomer component comprises a free radical polymerizable methacrylic monomer. 20. The method of embodiment 19, wherein the polymerizable component is capable of being polymerized in a blending process.
[0129] Embodiment 24. The pre-adhesive tackifier component is selected from the group consisting of C5, C9, C5 / C9, dicyclopentadiene, tadiene, terpene, or hydrogenated resins thereof, or combinations thereof; 20. The method of embodiment 19.
[0130] Embodiment 25. The pre-adhesive mixture comprises at least about 2.0% by weight, at least about 3.0% by weight, or at least about 4.0% by weight, or At least about 5.0% by weight, or at least about 6.0% by weight, or at least about 7. 0% by weight, or at least about 8.0% by weight, or at least about 9.0% by weight, or at least about 10.0% by weight, or at least about 12.5% by weight, or at least about 15.0% by weight, or at least about 17.5% by weight, or at least about or less 20. The method of embodiment 19, wherein each of the pre-adhesive macromonomer components comprises about 20.0% by weight of the pre-adhesive macromonomer component. Law.
[0131] Embodiment 26. The pre-adhesive mixture comprises about 40% by weight of the pre-adhesive mixture based on the total weight of the pre-adhesive mixture. % or less, about 39% or less by weight, or about 38% or less by weight, or about 37% or less by weight, or About 36% by weight or less, or about 35% by weight or less, or about 34% by weight or less, or about 33% by weight or less % by weight or less, or about 32% by weight or less, or about 31% by weight or less, or about 30% by weight or less or about 29% by weight or less, or about 28% by weight or less, or about 27% by weight or less, or A pre-adhesive macromonomer component having about 26% or less by weight, or about 25% or less by weight, 20. The method according to embodiment 19.
[0132] Embodiment 27. The pre-adhesive mixture comprises at least about 50% by weight, at least about 52% by weight %, or at least about 55% by weight, or at least about 57% by weight, or at least about 60.0% by weight, or at least about 62% by weight, or at least about 65% by weight, or at least about 67% by weight, or at least about 70.0% by weight, or at least about 72% by weight, or at least about 75% by weight, or at least about 77% by weight of pre-bonded 20. The method of embodiment 19, comprising the step of:
[0133] Embodiment 28. The pre-adhesive mixture is about 90% by weight or less, about 88% by weight or less, or about 8 5% by weight or less, or 83% by weight or less, or 80% by weight or less, or 78% by weight or less 20. The method of embodiment 19, comprising a pre-adhesive (meth)acrylic polymer component A.
[0134] Embodiment 29. The pre-adhesive mixture comprises at least about 0.1% by weight, at least about 0.5% by weight, or at least about 1.0% by weight, or At least about 1.5% by weight, or at least about 2.0% by weight, or at least about 2. 5% by weight, or at least about 3.0% by weight, or at least about 3.5% by weight, or At least about 4.0% by weight, or at least about 4.5% by weight, or at least about 5. 0% by weight, or at least about 5.5% by weight, or at least about 6.0% by weight, or At least about 6.5% by weight, or at least about 7.0% by weight, or at least about 7. 5% by weight, or at least about 8.0% by weight, or at least about 8.5% by weight, or At least about 9.0% by weight, or at least about 9.5% by weight, or at least about 10 20. The method of embodiment 19, comprising .0% by weight of a pre-adhesive tackifier component.
[0135] Embodiment 30. The pre-adhesive mixture comprises about 30 weight percent of the pre-adhesive mixture based on the total weight of the pre-adhesive mixture. % or less, about 28% or less by weight, or 25% or less by weight, or 23% or less by weight, or 20 % by weight or less, or 18% by weight or less, or 15% by weight or less, or 13% by weight or less, 20. The method of claim 19, further comprising 11 or less by weight of a pre-adhesive mixture tackifier component. Law.
[0136] Embodiment 31. Pre-adhesive (meth)acrylic polymer component A is a pre-adhesive (meth)acrylic polymer component B. At least about 0.1% by weight, based on the total weight of the acrylic polymer component A, at least about 0.5% by weight, or at least about 1.0% by weight, or at least about 1.5% by weight, or at least about 2.0%, or at least about 2.5%, or at least about 3.0% by weight, or at least about 3.5% by weight, or at least about 4.0% by weight, or at least about 4.5%, or at least about 5.0%, or at least about 5.5 wt. %, or at least about 6.0 wt. % of pre-adhesive monomer component a1; 21. The method of embodiment 20.
[0137] Embodiment 32. Pre-adhesive (meth)acrylic polymer component A is a pre-adhesive (meth)acrylic polymer component B. About 10.0% by weight or less, about 9.5% by weight or less based on the total weight of the acrylic polymer component A or less than about 9.0% by weight, or less than about 8.5% by weight, or less than about 8.0% by weight or about 7.5% by weight or less, or about 7.0% by weight or less, or about 6.5% by weight or less; or about 6.0% by weight or less, or about 5.5% by weight or less, or about 5.0% by weight or less, or about 4.5% by weight or less, or about 4.0% by weight or less, or about 3.5% by weight or less, 21. The method of claim 20, wherein the pre-adhesive monomer component a1 comprises about 3.0% by weight or less. .
[0138] Embodiment 33. Pre-adhesive (meth)acrylic polymer component A is a pre-adhesive (meth)acrylic polymer component B. At least about 80% by weight, at least about 8% by weight, based on the total weight of the acrylic polymer component A 2% by weight, or at least about 85% by weight, or at least about 87% by weight, or less at least about 90%, or at least about 92%, or at least about 95%, or at least about 97% by weight of pre-adhesive monomer component a2. Method of posting.
[0139] Embodiment 34. Pre-adhesive (meth)acrylic polymer component A is a pre-adhesive (meth)acrylic polymer component B. About 99% by weight or less of the pre-adhesive monomer component based on the total weight of the acrylic polymer component A 21. The method of embodiment 20, comprising component a2.
[0140] Embodiment 35. The adhesive composition comprises at least about 1 weight percent of the total weight of the adhesive composition. % and 40% by weight or less of the macromonomer component, and a small amount based on the total weight of the adhesive composition. and at least about 50% by weight and at most about 98% by weight of a (meth)acrylic polymer component A, At least about 0.1% by weight and no more than about 30% by weight of the adhesive composition. and a macromonomer component having a weight average molecular weight of at least 1000 g / mol. the macromonomer component having a glass transition temperature of at least about 40° C.; The (meth)acrylic polymer component A has a glass transition temperature (Tg) of about 20° C. or less. 20. The method of embodiment 19.
[0141] Embodiment 36. The graft copolymer of the adhesive structure comprises a main chain portion and a graft side chain portion. The main chain portion contains a (meth)acrylic polymer component A, and the graft side chain portion contains 36. The method of embodiment 35, comprising a macromonomer component.
[0142] Embodiment 37. The graft copolymer of the adhesive structure is formed via radiation-initiated polymerization. 36. The method of embodiment 35, wherein
[0143] Embodiment 38: The (meth)acrylic polymer component A is a (meth)acrylic polymer component At least about 0.1% by weight and not more than about 10% by weight of monomer components based on the total weight of component A The component a1 includes an ethylenically unsaturated functional monomer having a pendant hydrogen bonding group. At least about 100% by weight of the monomer component a1 and the (meth)acrylic polymer component A, and about 80% by weight or less and about 99% by weight or less of monomer component a2, and a reaction product of a polymerizable material comprising a monomer component a2, the monomer component a2 comprising a monomer. 36. The method of embodiment 35.
[0144] Embodiment 39. The monomer component a1 is an acid-containing (meth)acrylic monomer (acrylic acid, Methacrylic acid, 2-carboxyethyl acrylate, etc.), hydroxy-containing (meth)acrylic (2-hydroxyethyl (meth)acrylate), primary, secondary, or Nitrogen-containing monomers with tertiary amino groups, and primary, secondary, or tertiary amides an ethylenically unsaturated functional monomer selected from the group consisting of nitrogen-containing monomers having a 39. The method of embodiment 38, comprising:
[0145] Embodiment 40. The monomer component a2 is an acrylic acid ester of the formula C=C(R2)(COOR1). esters, where R1 is an alkyl group containing 1 to 24 carbons and R2 is 39. The method of embodiment 38, wherein N is H or methyl.
[0146] Embodiment 41. The macromonomer component is a (meth)acrylic copolymer having pendant alicyclic functional groups. and the macromonomer component comprises a copolymerizable monomer, the copolymerizable monomer being polymerized in a free radical polymerization process. 36. The method of embodiment 35, wherein the
[0147] Embodiment 42. The tackifier component is selected from the group consisting of C5, C9, C5 / C9, dicyclopentadiene, 3. The composition of claim 3, further comprising a terpene, or a hydrogenated resin thereof, or a combination thereof. 5. The method according to claim 5.
[0148] Embodiment 43. The adhesive composition comprises at least about 2.0 based on the total weight of the adhesive composition. %, at least about 3.0%, or at least about 4.0%, or at least or at least about 5.0% by weight, or at least about 6.0% by weight, or at least about 7.0% by weight %, or at least about 8.0% by weight, or at least about 9.0% by weight, or at least at least about 10.0% by weight, or at least about 12.5% by weight, or at least about 15.0% by weight % by weight, or at least about 17.5% by weight, or at least about 2 36. The method of embodiment 35, comprising 0.0 wt. % of the macromonomer component.
[0149] Embodiment 44. The adhesive composition comprises about 40% by weight or less of the total weight of the adhesive composition. About 39% by weight or less, or about 38% by weight or less, or about 37% by weight or less, or about 36% by weight or less % by weight or less, or about 35% by weight or less, or about 34% by weight or less, or about 33% by weight or less or about 32% by weight or less, or about 31% by weight or less, or about 30% by weight or less, or About 29% by weight or less, or about 28% by weight or less, or about 27% by weight or less, or about 26% by weight or less 36. The composition of claim 35, comprising no more than about 25% by weight of the macromonomer component. method.
[0150] Embodiment 45. The adhesive composition comprises at least about 50% by weight, at least about 52% by weight, Or at least about 55% by weight, or at least about 57% by weight, or at least about 6 0.0% by weight, or at least about 62% by weight, or at least about 65% by weight, or At least about 67% by weight, or at least about 70.0% by weight, or at least about 72 %, or at least about 75%, or at least about 77%, or less by weight The method according to embodiment 35, wherein each of the (meth)acrylic polymer components A comprises about 80% by weight of the (meth)acrylic polymer component A. Law.
[0151] Embodiment 46. The adhesive composition comprises about 90% by weight or less, about 88% by weight or less, or about 85% by weight or less. % by weight or less, or 83% by weight or less, or 80% by weight or less, or 78% by weight or less (Me The method of embodiment 35, comprising the step of: (a) forming an acrylic polymer component A;
[0152] Embodiment 47. The adhesive composition comprises at least about 0.1 %, at least about 0.5%, or at least about 1.0%, or at least or at least about 1.5%, or at least about 2.0%, or at least about 2.5% by weight %, or at least about 3.0%, or at least about 3.5%, or at least or at least about 4.0% by weight, or at least about 4.5% by weight, or at least about 5.0% by weight %, or at least about 5.5%, or at least about 6.0%, or at least or at least about 6.5%, or at least about 7.0%, or at least about 7.5% by weight %, or at least about 8.0%, or at least about 8.5%, or at least or at least about 9.0%, or at least about 9.5%, or at least about 10% by weight The method of embodiment 35, comprising a tackifier component.
[0153] Embodiment 48. The adhesive composition comprises about 30% by weight or less of the total weight of the adhesive composition. About 28% by weight or less, or 25% by weight or less, or 23% by weight or less, or 20% by weight or less or less than 18% by weight, or less than 15% by weight, or less than 13% by weight, or less than 11% by weight 36. The method of embodiment 35, comprising up to 50% by weight of a tackifier component.
[0154] Embodiment 49. The (meth)acrylic polymer component A is a (meth)acrylic polymer component at least about 0.1% by weight, at least about 0.5% by weight, based on the total weight of part A; or At least about 1.0% by weight, or at least about 1.5% by weight, or at least about 2. 0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight, or At least about 3.5% by weight, or at least about 4.0% by weight, or at least about 4. 5% by weight, or at least about 5.0% by weight, or at least about 5.5% by weight, or 39. The method of embodiment 38, comprising at least about 6.0% by weight of monomer component a1.
[0155] Embodiment 50. The (meth)acrylic polymer component A is a (meth)acrylic polymer component About 10.0% by weight or less, about 9.5% by weight or less, or about 9.0% by weight or less, based on the total weight of component A % by weight or less, or about 8.5% by weight or less, or about 8.0% by weight or less, or about 7.5% by weight or less % or less, or about 7.0% by weight or less, or about 6.5% by weight or less, or about 6.0% by weight or less or less than about 5.5% by weight, or less than about 5.0% by weight, or less than about 4.5% by weight or less than about 4.0% by weight, or less than about 3.5% by weight, or less than about 3.0% by weight 39. The method of embodiment 38, comprising the monomer component a1 of
[0156] Embodiment 51. The (meth)acrylic polymer component A is a (meth)acrylic polymer component At least about 80% by weight, at least about 82% by weight, or less, based on the total weight of component A at least about 85%, or at least about 87%, or at least about 90%, Or at least about 92% by weight, or at least about 95% by weight, or at least about 9 39. The method of embodiment 38, comprising 7% by weight of monomer component a2.
[0157] Embodiment 52. The (meth)acrylic polymer component A comprises about 99% by weight or less. 39. The method of claim 38.
[0158] Embodiment 53. A single layer foam tape comprising a foam core containing hollow microspheres in an adhesive. The adhesive comprises an adhesive structure and an adhesive composition, the adhesive structure comprising a graphite layer. and the adhesive composition comprises a copolymer, the copolymer being at least about 1% by weight and 40% by weight or less of the macromonomer component, based on the total weight of the adhesive composition , at least about 50% by weight and not more than about 98% by weight of (meth)acrylic polymer component A and at least about 0.1 wt. % and no more than about 30 wt. % based on the total weight of the adhesive composition. and a tackifier component of at least 1000 g / mol. The macromonomer component has a glass transition temperature of at least about 40° C. (Meth)acrylic polymer component A has a glass transition temperature (Tg) of about 20° C. or less. A single layer foam tape.
[0159] Embodiment 54. The graft copolymer of the adhesive structure comprises a main chain portion and a graft side chain portion. The main chain portion contains a (meth)acrylic polymer component A, and the graft side chain portion contains 54. The monolayer foam tape of embodiment 53, comprising a macromonomer component.
[0160] Embodiment 55. The graft copolymer of the adhesive structure is formed via radiation-initiated polymerization. 54. The monolayer foam tape of embodiment 53.
[0161] Embodiment 56: (Meth)acrylic polymer component A is a (meth)acrylic polymer component At least about 0.1% by weight and not more than about 10% by weight of monomer components based on the total weight of component A The component a1 includes an ethylenically unsaturated functional monomer having a pendant hydrogen bonding group. At least about 100% by weight of the monomer component a1 and the (meth)acrylic polymer component A, and about 80% by weight or less and about 99% by weight or less of monomer component a2, and a reaction product of a polymerizable material comprising a monomer component a2, the monomer component a2 comprising a monomer. 54. The monolayer foam tape of embodiment 53.
[0162] Embodiment 57. The monomer component a1 is an acid-containing (meth)acrylic monomer (acrylic acid, Methacrylic acid, 2-carboxyethyl acrylate, etc.), hydroxy-containing (meth)acrylic (2-hydroxyethyl (meth)acrylate), primary, secondary, or Nitrogen-containing monomers with tertiary amino groups, and primary, secondary, or tertiary amides an ethylenically unsaturated functional monomer selected from the group consisting of nitrogen-containing monomers having a 57. The monolayer foam tape of embodiment 56, comprising:
[0163] Embodiment 58. The monomer component a2 is an acrylic acid ester of the formula C=C(R2)(COOR1). esters, where R1 is an alkyl group containing 1 to 24 carbons and R2 is 57. The monolayer foam tape of embodiment 56, wherein H is H or methyl.
[0164] Embodiment 59. The macromonomer component is a (meth)acrylic copolymer having pendant alicyclic functional groups. and the macromonomer component comprises a copolymerizable monomer, the copolymerizable monomer being polymerized in a free radical polymerization process. 54. The monolayer foam tape of embodiment 53, which can be combined with a
[0165] Embodiment 60. The tackifier component is selected from the group consisting of C5, C9, C5 / C9, dicyclopentadiene, 5. The composition of claim 5, further comprising a terpene, or a hydrogenated resin thereof, or a combination thereof. 4. The monolayer foam tape according to claim 3.
[0166] Embodiment 61. The adhesive composition comprises at least about 2.0 based on the total weight of the adhesive composition. %, at least about 3.0%, or at least about 4.0%, or at least or at least about 5.0% by weight, or at least about 6.0% by weight, or at least about 7.0% by weight %, or at least about 8.0% by weight, or at least about 9.0% by weight, or at least at least about 10.0% by weight, or at least about 12.5% by weight, or at least about 15.0% by weight % by weight, or at least about 17.5% by weight, or at least about 2 54. The monolayer foam tape of embodiment 53, comprising 0.0 wt.% of the macromonomer component.
[0167] Embodiment 62. The adhesive composition comprises about 40% by weight or less of the total weight of the adhesive composition. About 39% by weight or less, or about 38% by weight or less, or about 37% by weight or less, or about 36% by weight or less % by weight or less, or about 35% by weight or less, or about 34% by weight or less, or about 33% by weight or less or about 32% by weight or less, or about 31% by weight or less, or about 30% by weight or less, or About 29% by weight or less, or about 28% by weight or less, or about 27% by weight or less, or about 26% by weight or less 54. The composition of claim 53, comprising no more than about 25% by weight of the macromonomer component. Single layer foam tape.
[0168] Embodiment 63. The adhesive composition comprises at least about 50% by weight, at least about 52% by weight, Or at least about 55% by weight, or at least about 57% by weight, or at least about 6 0.0% by weight, or at least about 62% by weight, or at least about 65% by weight, or At least about 67% by weight, or at least about 70.0% by weight, or at least about 72 %, or at least about 75%, or at least about 77%, or less by weight 54. The method according to claim 53, wherein each of the (meth)acrylic polymer components A and the (meth)acrylic polymer component B comprises about 80% by weight of the (meth)acrylic polymer component A. Layer foam tape.
[0169] Embodiment 64. The adhesive composition comprises about 90% by weight or less, about 88% by weight or less, or about 85% by weight or less. % by weight or less, or 83% by weight or less, or 80% by weight or less, or 78% by weight or less (Me The monolayer foam tape of embodiment 53, comprising an acrylic polymer component A.
[0170] Embodiment 65. The adhesive composition comprises at least about 0.1% by weight of the total adhesive composition. %, at least about 0.5%, or at least about 1.0%, or at least or at least about 1.5%, or at least about 2.0%, or at least about 2.5% by weight %, or at least about 3.0%, or at least about 3.5%, or at least or at least about 4.0% by weight, or at least about 4.5% by weight, or at least about 5.0% by weight %, or at least about 5.5%, or at least about 6.0%, or at least or at least about 6.5%, or at least about 7.0%, or at least about 7.5% by weight %, or at least about 8.0%, or at least about 8.5%, or at least or at least about 9.0%, or at least about 9.5%, or at least about 10% by weight 54. A monolayer foam tape as described in embodiment 53, comprising a tackifier component.
[0171] Embodiment 66. The adhesive composition comprises about 30% by weight or less of the total weight of the adhesive composition. About 28% by weight or less, or 25% by weight or less, or 23% by weight or less, or 20% by weight or less or less than 18% by weight, or less than 15% by weight, or less than 13% by weight, or less than 11% by weight 54. The monolayer foam tape of embodiment 53, comprising up to about 100% by weight of a tackifier component.
[0172] Embodiment 67. The (meth)acrylic polymer component A is a (meth)acrylic polymer component at least about 0.1% by weight, at least about 0.5% by weight, based on the total weight of part A; or At least about 1.0% by weight, or at least about 1.5% by weight, or at least about 2. 0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight, or At least about 3.5% by weight, or at least about 4.0% by weight, or at least about 4. 5% by weight, or at least about 5.0% by weight, or at least about 5.5% by weight, or The monolayer film according to embodiment 56, comprising at least about 6.0% by weight of monomer component a1. Mutape.
[0173] Embodiment 68. The (meth)acrylic polymer component A is a (meth)acrylic polymer component About 10.0% by weight or less, about 9.5% by weight or less, or about 9.0% by weight or less, based on the total weight of component A % by weight or less, or about 8.5% by weight or less, or about 8.0% by weight or less, or about 7.5% by weight or less % or less, or about 7.0% by weight or less, or about 6.5% by weight or less, or about 6.0% by weight or less or less than about 5.5% by weight, or less than about 5.0% by weight, or less than about 4.5% by weight or less than about 4.0% by weight, or less than about 3.5% by weight, or less than about 3.0% by weight 57. The monolayer foam tape of embodiment 56, comprising monomer component a1 of:
[0174] Embodiment 69. The (meth)acrylic polymer component A is a (meth)acrylic polymer component At least about 80% by weight, at least about 82% by weight, or less, based on the total weight of component A at least about 85%, or at least about 87%, or at least about 90%, Or at least about 92% by weight, or at least about 95% by weight, or at least about 9 57. The monolayer foam tape of embodiment 56, comprising 7 wt.-% of monomer component a2.
[0175] Embodiment 70. The (meth)acrylic polymer component A is a (meth)acrylic polymer component 57. The method of claim 56, further comprising: Single layer foam tape.
[0176] Embodiment 71. The monolayer foam tape has a thickness of at least about 0.125 mm. 54. A monolayer foam tape as described in embodiment 53.
[0177] Embodiment 72. An embodiment in which the single layer foam tape has a thickness of about 0.25 mm or less. 54. A monolayer foam tape as described in 53.
[0178] Embodiment 73. The hollow spheres are glass beads, polymeric microspheres, or a combination thereof. 54. The monolayer foam tape of embodiment 53, comprising:
[0179] Embodiment 74. A foam tape comprising hollow microspheres within the foam material. a foam core and a first adhesive layer of a first adhesive covering a first surface of the foam core; The first adhesive comprises a first adhesive structure and a first adhesive composition, The structure includes a graft copolymer, and the first adhesive composition comprises a total weight of the first adhesive composition. at least about 1% by weight and no more than 40% by weight of a first macromonomer component; At least about 50% by weight and at least about 98% by weight based on the total weight of the first adhesive composition. Based on the total weight of the first (meth)acrylic polymer component A and the first adhesive composition at least about 0.1 wt. % and no more than about 30 wt. % of a first tackifier component; The first macromonomer component has a weight average molecular weight of at least 1000 g / mol. , the first macromonomer component has a glass transition temperature of at least about 40 ° C., and the first ( The meth)acrylic polymer component A has a glass transition temperature (Tg) of about 20°C or less; Foam tape.
[0180] Embodiment 75. The graft copolymer of the first adhesive structure comprises a backbone portion and a graft The main chain portion contains a first (meth)acrylic polymer component A, and the side chain portion contains a first (meth)acrylic polymer component B. 75. The foam tape of embodiment 74, wherein the side chain portion comprises a first macromonomer component. .
[0181] Embodiment 76. The graft copolymer of the first adhesive structure is prepared by polymerization via radiation-initiated polymerization. 75. The foam tape of embodiment 74, which is formed.
[0182] Embodiment 77. The first (meth)acrylic polymer component A is a first (meth)acrylic At least about 0.1% by weight and no more than about 10% by weight based on the total weight of the system polymer component A The first monomer component a1 has an ethylenically unsaturated group having a pendant hydrogen bonding group. A first monomer component a1 containing a functional monomer and a first (meth)acrylic polymer component At least about 80% by weight and no more than about 99% by weight of the first monomer, based on the total weight of part A a first monomer component a2 comprising an ethylenically unsaturated monomer; 75. The foam tape of embodiment 74, comprising the reaction product of a polymerizable material comprising:
[0183] Embodiment 78. The first monomer component a1 is an acid-containing (meth)acrylic monomer (acrylic acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, etc.), hydroxy-containing (methacrylic acid, 2-carboxyethyl acrylate, etc.) ) Acrylic monomer (2-hydroxyethyl (meth)acrylate), primary, secondary, or nitrogen-containing monomers having a tertiary amino group, and primary, secondary, or tertiary Ethylenically unsaturated functional monomers selected from the group consisting of nitrogen-containing monomers having amide groups. 78. The foam tape of embodiment 77, comprising a monomer.
[0184] Embodiment 79. The first monomer component a2 is an acrylic acid having the formula C=C(R2)(COOR1). R1 is an alkyl group containing 1 to 24 carbons; The foam tape of embodiment 77, wherein 2 is H or methyl.
[0185] Embodiment 80. The first macromonomer component has pendant alicyclic functional groups (meth ) an acrylic monomer, and the macromonomer component is 75. The foam tape of embodiment 74, wherein the foam tape is capable of being polymerized by heating.
[0186] Embodiment 81. The first tackifier component is a C5, C9, C5 / C9, dicyclopentadiene ene, terpene, or hydrogenated resins thereof, or combinations thereof 75. The foam tape of claim 74.
[0187] Embodiment 82. The first adhesive composition comprises at least at least about 2.0%, at least about 3.0%, or at least about 4.0% by weight, or at least about 5.0% by weight, or at least about 6.0% by weight, or at least about 7.0% by weight, or at least about 8.0% by weight, or at least about 9.0% by weight, or at least about 10.0%, or at least about 12.5%, or at least at least about 15.0% by weight, or at least about 17.5% by weight, or at least about or less 75. The process of embodiment 74, comprising at least about 20.0 wt.% of the first macromonomer component. Foam tape.
[0188] Embodiment 83. The first adhesive composition comprises about 40% by weight of the first adhesive composition. % by weight or less, about 39% by weight or less, about 38% by weight or less, or about 37% by weight or less, or about 36% by weight or less, or about 35% by weight or less, or about 34% by weight or less, or about 3 3% by weight or less, or about 32% by weight or less, or about 31% by weight or less, or about 30% by weight or less than about 29% by weight, or less than about 28% by weight, or less than about 27% by weight, or about 26% by weight or less, or about 25% by weight or less of the first macromonomer component. 75. The foam tape of embodiment 74.
[0189] Embodiment 84. The first adhesive composition comprises at least one first adhesive component A based on the total weight of the first adhesive component A. At least about 50% by weight, at least about 52% by weight, or at least about 55% by weight, or At least about 57% by weight, or at least about 60.0% by weight, or at least about 62% by weight %, or at least about 65%, or at least about 67%, or at least at least about 70.0% by weight, or at least about 72% by weight, or at least about 75% by weight, or at least about 77% by weight, or at least about 80% by weight of the first (meth)acrylic acid. 75. The foam tape of embodiment 74, comprising an alkyl-based polymer component A.
[0190] Embodiment 85. The first adhesive composition comprises about 90% by weight of the first adhesive composition. % by weight or less, about 88% by weight or less, or 85% by weight or less, or 83% by weight or less, or 80% by weight or less, or 78% by weight or less of a first (meth)acrylic polymer component A 75. The foam tape of embodiment 74.
[0191] Embodiment 86. The first adhesive composition comprises at least at least about 0.1%, at least about 0.5%, or at least about 1.0%, or at least about 1.5%, or at least about 2.0%, or at least about 2.5% by weight, or at least about 3.0% by weight, or at least about 3.5% by weight, or at least about 4.0%, or at least about 4.5%, or at least about 5.0% by weight, or at least about 5.5% by weight, or at least about 6.0% by weight, or at least about 6.5%, or at least about 7.0%, or at least about 7.5% by weight, or at least about 8.0% by weight, or at least about 8.5% by weight, or or at least about 9.0%, or at least about 9.5%, or at least about 75. The foam tape of embodiment 74, comprising 10% by weight of the first tackifier component.
[0192] Embodiment 87. The adhesive composition comprises about 30% by weight of the first adhesive composition based on the total weight of the first adhesive composition. or less, about 28% by weight or less, or 25% by weight or less, or 23% by weight or less, or 20% by weight or less % by weight or less, or 18% by weight or less, or 15% by weight or less, or 13% by weight or less, 75. The foam tape of embodiment 74, comprising 11 wt.% or less of the first tackifier component. .
[0193] Embodiment 88. The first (meth)acrylic polymer component A is a first (meth)acrylic At least about 0.1% by weight, at least about 0.5% by weight, based on the total weight of the system polymer component A %, or at least about 1.0%, or at least about 1.5%, or less At least about 2.0%, or at least about 2.5%, or at least about 3.0% by weight. %, or at least about 3.5%, or at least about 4.0%, or less At least about 4.5% by weight, or at least about 5.0% by weight, or at least about 5.5% by weight %, or at least about 6.0% by weight of the first monomer component a1, The foam tape according to claim 1.
[0194] Embodiment 89. The first (meth)acrylic polymer component A is a first (meth)acrylic About 10.0% by weight or less, about 9.5% by weight or less, or about 9.0% by weight or less, or about 8.5% by weight or less, or about 8.0% by weight or less, or about 7.5% by weight or less, or about 7.0% by weight or less, or about 6.5% by weight or less, or about 6.0% by weight or less, or about 5.5% by weight or less, or about 5.0% by weight or less, or about 4 .5% by weight or less, or about 4.0% by weight or less, or about 3.5% by weight or less, or about 3. 78. The foam tape of embodiment 77, comprising up to 0 wt.% of the first monomer component a1.
[0195] Embodiment 90. The first (meth)acrylic polymer component A is a first (meth)acrylic At least about 80% by weight, at least about 82% by weight, based on the total weight of the system polymer component A %, or at least about 85%, or at least about 87%, or at least about 90% by weight, or at least about 92% by weight, or at least about 95% by weight, or The foam according to embodiment 77, comprising at least about 97% by weight of the first monomer component a2. tape.
[0196] Embodiment 91. The first (meth)acrylic polymer component A comprises about 99% by weight or less 78. The foam tape of embodiment 77.
[0197] Embodiment 92. A foam tape is provided having a first layer of a second adhesive covering a second surface of the foam core. The adhesive further comprises a second adhesive layer, the second adhesive comprising a second adhesive structure and a second adhesive set. the second adhesive structure comprises a graft copolymer, and the second adhesive composition comprises , at least about 1 wt. % and no more than 40 wt. %, based on the total weight of the second adhesive composition the second macromonomer component and the second adhesive composition, % by weight and up to about 98% by weight of a second (meth)acrylic polymer component A; At least about 0.1% by weight and no more than about 30% by weight of the second adhesive composition, based on the total weight of the adhesive composition. and a second macromonomer component of at least 1000 g / m the second macromonomer component has a weight average molecular weight of at least about 40° C. The second (meth)acrylic polymer component A has a glass transition temperature of about 20° C. or less. 75. The foam tape of embodiment 74, having a transition temperature (Tg).
[0198] Embodiment 93. The graft copolymer of the second adhesive structure comprises a backbone portion and a graft The main chain portion contains a second (meth)acrylic polymer component A, and the side chain portion contains a second (meth)acrylic polymer component B. 93. The foam tape of embodiment 92, wherein the side chain portion comprises a second macromonomer component. .
[0199] Embodiment 94. The graft copolymer of the second adhesive structure is prepared by polymerization via radiation-initiated polymerization. 93. The foam tape of embodiment 92, which is formed.
[0200] Embodiment 95. The second (meth)acrylic polymer component A is a second (meth)acrylic At least about 0.1% by weight and no more than about 10% by weight based on the total weight of the system polymer component A The second monomer component a1 is an ethylenically unsaturated monomer having a pendant hydrogen bonding group. A second monomer component a1 containing a functional monomer and a second (meth)acrylic polymer component At least about 80% by weight and not more than about 99% by weight of the second monomer, based on the total weight of component A. a second monomer component a2, the second monomer component a2 comprising an ethylenically unsaturated monomer; 93. The foam tape of embodiment 92, comprising the reaction product of a polymerizable material comprising:
[0201] Embodiment 96. The second monomer component a1 is an acid-containing (meth)acrylic monomer (acrylic acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, etc.), hydroxy-containing (methacrylic acid, 2-carboxyethyl acrylate, etc.) ) Acrylic monomer (2-hydroxyethyl (meth)acrylate), primary, secondary, or nitrogen-containing monomers having a tertiary amino group, and primary, secondary, or tertiary Ethylenically unsaturated functional monomers selected from the group consisting of nitrogen-containing monomers having amide groups. 96. The foam tape of embodiment 95, comprising a monomer.
[0202] Embodiment 97. The second monomer component a2 is an acrylic acid having the formula C=C(R2)(COOR1). R1 is an alkyl group containing 1 to 24 carbons; The foam tape of embodiment 95, wherein 2 is H or methyl.
[0203] Embodiment 98. The second macromonomer component has pendant alicyclic functional groups (meth ) an acrylic monomer, and the macromonomer component is 93. The foam tape of embodiment 92, wherein the foam tape is capable of being polymerized by heating.
[0204] Embodiment 99. The second tackifier component is a C5, C9, C5 / C9, dicyclopentadiene ene, terpene, or hydrogenated resins thereof, or combinations thereof 93. The foam tape of claim 92.
[0205] Embodiment 100. The second adhesive composition comprises at least about 100% by weight of the second adhesive composition. at least about 2.0% by weight, at least about 3.0% by weight, or at least about 4.0% by weight, or at least about 5.0% by weight, or at least about 6.0% by weight, or at least about 7.0% by weight, or at least about 8.0% by weight, or at least about 9.0% by weight, or at least about 10.0% by weight, or at least about 12.5% by weight, or less At least about 15.0% by weight, or at least about 17.5% by weight, or at least about 93. The composition of claim 92, comprising at least about 20.0 wt. % of the second macromonomer component. Foam tape.
[0206] Embodiment 101. The second adhesive composition comprises about 4% by weight of the second adhesive composition. 0% by weight or less, about 39% by weight or less, or about 38% by weight or less, or about 37% by weight or less; or about 36% by weight or less, or about 35% by weight or less, or about 34% by weight or less, or about 33% by weight or less, or about 32% by weight or less, or about 31% by weight or less, or about 30% by weight or less % or less, or about 29% or less by weight, or about 28% or less by weight, or about 27% or less by weight, or about 26% by weight or less, or about 25% by weight or less of a second macromonomer component; 93. The foam tape of embodiment 92.
[0207] Embodiment 102. The second adhesive composition comprises at least at least about 50% by weight, at least about 52% by weight, or at least about 55% by weight, or At least about 57% by weight, or at least about 60.0% by weight, or at least about 62 %, or at least about 65%, or at least about 67%, or less by weight At least about 70.0% by weight, or at least about 72% by weight, or at least about 75% by weight or at least about 77% by weight, or at least about 80% by weight of the second (meth)acrylic acid. 93. The foam tape of embodiment 92, comprising a copolymer-based polymer component A.
[0208] Embodiment 103. The second adhesive composition comprises about 9.0% by weight of the second adhesive composition. 0% or less by weight, about 88% or less by weight, or 85% or less by weight, or 83% or less by weight, or less than 80% by weight, or less than 78% by weight of a second (meth)acrylic polymer component A. 93. The foam tape of embodiment 92, comprising
[0209] Embodiment 104. The second adhesive composition comprises at least at least about 0.1%, at least about 0.5%, or at least about 1.0%, or at least about 1.5% by weight, or at least about 2.0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight, or at least about 3.5% by weight; or at least about 4.0% by weight, or at least about 4.5% by weight, or at least about 5.0% by weight, or at least about 5.5% by weight, or at least about 6.0% by weight; or at least about 6.5% by weight, or at least about 7.0% by weight, or at least about 7.5% by weight, or at least about 8.0% by weight, or at least about 8.5% by weight; or at least about 9.0% by weight, or at least about 9.5% by weight, or at least 93. The foam tape of embodiment 92, comprising about 10% by weight of the second tackifier component.
[0210] Embodiment 105. The adhesive composition comprises about 30% by weight of the second adhesive composition based on the total weight of the second adhesive composition. % or less, about 28% or less by weight, or 25% or less by weight, or 23% or less by weight, or 20 % by weight or less, or 18% by weight or less, or 15% by weight or less, or 13% by weight or less, 93. The foam tape of embodiment 92, comprising 10 or less than 11 wt. % of a second tackifier component. P.S.
[0211] Embodiment 106. The second (meth)acrylic polymer component A is a second (meth)acrylic At least about 0.1% by weight, at least about 0.5% by weight, based on the total weight of the olefin-based polymer component A %, or at least about 1.0%, or at least about 1.5%, or less At least about 2.0% by weight, or at least about 2.5% by weight, or at least about 3.0% by weight %, or at least about 3.5%, or at least about 4.0%, or less At least about 4.5% by weight, or at least about 5.0% by weight, or at least about 5.5 %, or at least about 6.0% by weight of the second monomer component a1; 5. The foam tape according to claim 5.
[0212] Embodiment 107. The second (meth)acrylic polymer component A is a second (meth)acrylic about 10.0% by weight or less, about 9.5% by weight or less, or or about 9.0% by weight or less, or about 8.5% by weight or less, or about 8.0% by weight or less, about 7.5% by weight or less, or about 7.0% by weight or less, or about 6.5% by weight or less, or about 6.0% by weight or less, or about 5.5% by weight or less, or about 5.0% by weight or less, or about 4.5% by weight or less, or about 4.0% by weight or less, or about 3.5% by weight or less, or about 3 96. The foam tape of embodiment 95, comprising 0.0 wt.% or less of the second monomer component a1. .
[0213] Embodiment 108. The second (meth)acrylic polymer component A is a second (meth)acrylic At least about 80% by weight, at least about 82% by weight, based on the total weight of the olefin-based polymer component A %, or at least about 85% by weight, or at least about 87% by weight, or at least about 90% by weight, or at least about 92% by weight, or at least about 95% by weight, or The compound according to embodiment 95, which comprises at least about 97% by weight of the second monomer component a2. Mutape.
[0214] Embodiment 109. The second (meth)acrylic polymer component A comprises about 99% by weight or less. 96. The foam tape of embodiment 95. EXAMPLES
[0215] The concepts described herein are further illustrated in the following examples, which are incorporated herein by reference in their entirety. The claims do not limit the scope of the invention.
[0216] Test Method The following test methods were used to evaluate the adhesives of the present invention. All percentages, parts and ratios in the specification and claims are to be construed as if they were not otherwise specifically expressly stated. Weight percentages unless otherwise stated.
[0217] Test method A1: Strip of anodized aluminum (dimensions 19mm x 200mm x 0. 125 mm) to test adhesion of tape samples 10 mm wide and at least 100 mm long The pressure is applied to the aluminum by rolling with a 6.8 kg roller. The opposite side of the sample (the test side) is then coated with polypropylene or heptane. or isopropyl alcohol. The resulting mixture is firmly bonded to either the propylene diene terpolymer panel or the propylene diene terpolymer panel. After conditioning at 100% relative humidity for 24 hours, the sample was then moved against the adhesive surface at a speed of 30.5 cm / min. The aluminium strip is removed by pulling it at 90° to the ground. The test value is plus Remove tape from adhesive panels (adhesive delamination) or allow tape to cohesively shred Foam severance (FS) is reported as the force required to bond the material to the substrate. is the most desirable failure mode since it indicates greater internal strength than the foam layer.
[0218] Test Method B1: Apply the test adhesive side of a 2.54 cm x 2.54 cm piece of foam tape to Centered along the long edge of a 3" x 2" aluminum panel, 6 Wrap the other side of the foam tape (the test side) in a 7.62 cm x 7.62 cm 2 inches of polypropylene or either heptane or isopropyl alcohol on polypropylene-ethylene propylene diene terpolymer panels pre-cleaned with After conditioning for 24 hours at room temperature and 50% relative humidity, the assembly is Hang in a circulating oven preheated to 70°C for 15 minutes at 2° from the vertical. After the test, a 500 gram weight was immediately attached through a pre-drilled hole on the aluminum panel. The time it takes for the weight to fall is recorded over a period of several hours. After 10,000 minutes, a failure occurs. If this does not occur, the test is discontinued.
[0219] Test method B2: The test conditions were the same as B except that the oven was preheated to 80°C. Same as 1.
[0220] Test Method B3: The test conditions were the same as B except that the oven was preheated to 90°C. Same as 1.
[0221] Test method B4: The test conditions were the same except that the oven was preheated to 100°C. Same as B1.
[0222] Test Method C1: The test conditions were conditioned at room temperature and 50% relative humidity for 24 hours, followed by assemblies. The test was carried out in a circulating air oven at 80 °C for 72 hours. The assembly is then removed from the oven and cooled to room temperature and 5 The assembly is cooled for 1 hour at 0% relative humidity and then tested.
[0223] Test Method C2: The test conditions were conditioned at room temperature and 50% relative humidity for 24 hours, followed by assemblies. The assembly was left in an air-circulating oven at 90°C for 168 hours. The assembly is then removed from the oven and the assembly is Cool for 1 hour at room temperature and 50% relative humidity and then test.
[0224] Test Method D: The weight average molecular weight (Mw) and polydispersity index (PDI) of the sample were measured using gel immersion. The determination is made via gel permeation chromatography (GPC). Shimadzu Prominence LC-20AD system with refractive index detector The GPC was equipped with a set of oligomer columns, which were fitted with 10 narrow polydispersity polymers. Calibrated with styrene standards, 200 to 2×10 7 gmol-1 gave a linear calibration range of Tetrahydraforuan (THF, 1 mL) - 1 A flow rate of 1000 s was used as the waste liquid at 40° C. For each measurement, 30 mg of polymer was The solution was dissolved in 4 mL of THF and filtered through a 200 μm nylon filter before injection.
[0225] Test Method E: Glass Transition Temperature (T g ) by differential scanning calorimetry. Approximately 5 mg of each macromonomer was placed in a sealed The samples were placed in an aluminum pan and heated from 20 to 200 °C at a heating rate of 10 °C / min in two cycles. T g was determined from the change in heat flow during the second cycle.
[0226] Raw Materials: All chemicals are used as received without further purification or processing. It was done. [Table 1]
[0227] The adhesive was applied to a 50 micron PET film or to a 10% by weight acrylic acid, 90% by weight of 2-ethylhexyl acrylate, microspheres, and other commonly used Material: 0.9mm proprietary acrylic foam core Apply and cure.
[0228] Example 1: Samples S1 to S5 Sample adhesive compositions S1-S5 were formed according to embodiments described herein. The compositions of agents S1 to S5 are summarized in Table 1 below. [Table 2]
[0229] The macromonomers used in the adhesive compositions S1 to S5 are butyl acetate and was synthesized via cobalt-mediated catalytic chain transfer polymerization of isobornyl methacrylate using BOMA (50 g), AIBN (0.10 g), and butyl acetate (48 g) were mixed together in a In a 250 mL three-neck round-bottom flask were combined CoBF (2 mg) and butyl acetate. Acetate (10 g) was combined in a 20 mL scintillation vial and sonicated for 10 min. The CoBF catalyst required was decomposed with Depending on the amount, approximately 2-2.5 g of stock solution was then added to a 250 mL round-bottom flask containing the monomer The solution containing monomers, thermal initiator, and catalyst was then subjected to nitrogen gas pressure for 1 hour. The flask was then placed in a heated oil bath at 80° C. for 4.5 hours. The macromonomer was cooled under continuous stirring with a stir bar at 600 rpm. Precipitation in hot methanol / THF mixtures (methanol to THF ratio 20:1) The released macromonomer was then subjected to a vacuum oven set at 85°C. The samples were dried in a vacuum oven for 24 hours to remove most of the remaining organic volatile contaminants. The properties of the chromium monomers M1 to M4 are shown in Table 2. [Table 3]
[0230] Component A in sample adhesive compositions S1 to S5 was subjected to UV-initiated radical photopolymerization with 2-E It was prepared by copolymerizing a mixture of HA (389.9 g) and AA (10 g). BDK (0.1 g) was dissolved in the upper monomer mixture and then analyzed at 365 nm and 5 min. W / cm 2 The plates were purged with nitrogen gas for 1 hour before being exposed to UV light at 15-20°C. The polymerization was carried out until a temperature increase of 100° C. was observed. The resulting polymer component A was It had a viscosity of approximately 10,000 cP.
[0231] Sample adhesive composition S1 was prepared by first mixing the relevant macromonomer, component A, tackifier, IBO, A, BDK, and HDDA were combined in the amounts shown in Table 1. The different components are mixed until the macromonomer components are completely dissolved to produce syrup S1. The syrup was then poured onto the 0.9 mm acrylic foam core described above, or or 50 micron PET film, 365 nm, 5 mW / cm 2 Under UV light It was allowed to cure for 8 minutes to form an adhesive coating having a thickness of approximately 100 microns.
[0232] For sample adhesive compositions S2, S3, and S4, the relevant macromonomers are listed in Table 1. Prepared in the same manner as sample adhesive composition S1, except with substitutions as specified .
[0233] Example 2: Samples S5 to S7 Sample adhesive compositions S5 and S7 were formed according to embodiments described herein. The compositions S5 to S7 of the agent are summarized in Table 3 below. [Table 4]
[0234] The macromonomers used in the adhesive compositions S6 to S8 are referred to as macromonomers M1 to M2. A procedure similar to M5 was used to prepare cobalt methacrylate of isobornyl methacrylate in butyl acetate. The amount of IBOA comonomer was adjusted to different weight parts via catalytic chain transfer polymerization. The final macromonomer composition in percentages varies in macromonomers M5 to M7. The properties of the sample macromonomers M6 to M8 are shown in Table 4. [Table 5]
[0235] Component A in sample adhesive compositions S5 to S6 was subjected to UV-initiated radical photopolymerization with 2-E It was prepared by copolymerizing a mixture of HA (379.9 g) and AA (20 g). BDK (0.1 g) was dissolved in the upper monomer mixture and then analyzed at 365 nm and 5 min. W / cm 2 The plates were purged with nitrogen gas for 1 hour before being exposed to UV light at 15-20°C. The polymerization was carried out until a temperature increase of 100° C. was observed. The resulting polymer component A was The viscosity of the sample adhesive composition S7 was approximately 10,000 cP. Prepared as in Example 1.
[0236] Sample adhesive compositions S5 to S7 were prepared by placing the relevant macromonomers as specified in Table 3. The adhesive composition was prepared in the same manner as sample adhesive composition S1, except that the adhesive composition was replaced with a new one.
[0237] Example 3: Comparative Samples C1 to C3 Comparative sample adhesive compositions C1-C3 were prepared to demonstrate the graft copolymer-based adhesive properties described. The comparative sample adhesive compositions C1 to C3 are summarized in Table 5 below. can be. [Table 6]
[0238] The component B in the comparative adhesive composition was changed as follows: The chromium monomer component was replaced by the IBOMA monomer. In step 3, the macromonomer component is subjected to chain transfer in a heated water bath set at 80°C. As a photoinitiator, a standard non-reactive poly(isobutene) prepared via bulk photoinitiated polymerization in IOTG was used. The polymer properties are listed in Table 6 below. It is promised. [Table 7]
[0239] Component A in comparative adhesive compositions C1 to C3 was added according to the instructions given for sample adhesive S1. Comparative adhesive compositions C1 to C3 were prepared by mixing component B, component C1, and component C2 in the amounts shown in Table 5. Prepared by combining component A, tackifier, IBOA, BDK, and HDDA The different ingredients were added until component B was completely dissolved to prepare syrups C1 to C3. The syrup was then poured onto the 0.9 mm acrylic foam core as described above, and was applied onto a 50 micron PET film, at 365 nm and 5 mW / cm 2 8 Under UV Light The adhesive was allowed to cure for minutes to form an adhesive coating having a thickness of approximately 100 microns.
[0240] Low surface energy such as polypropylene and polypropylene / polyethylene copolymers The advantageous adhesion of our sample adhesives to substrates was evaluated using test method A1. The peel strengths of sample adhesives S1 to S7 and comparative adhesives C1 to C3 are summarized in Table 7 below. The abbreviation AD stands for adhesive failure and the abbreviation FS stands for foam cutting. [Table 8]
[0241] The data are for the present invention containing micromonomer components and graft copolymer structures. The adhesive works well on low surface energy substrates such as polypropylene / polyethylene. It is clearly shown to have peel adhesion.
[0242] The high internal cohesive strength of the present invention was also evaluated using a high temperature static shear test. The performance of adhesive samples S1 to S6 and comparative adhesives C1 to C3 in the shear test is summarized in Table 8. It is promised. [Table 9]
[0243] The data are for the present invention containing micromonomer components and graft copolymer structures. The adhesive has excellent internal cohesive strength and excellent static shear resistance up to 100°C The comparative adhesives showed high temperature static shear failure with rapid creep and failure in less than 6 hours. Doesn't pass any of the tests.
[0244] The adhesives of the present invention also possess a graft copolymer structure, which prevents degradation and adhesion of the tackifier component. This is achieved by increasing the mobility of the tackifier components, providing excellent resistance to adhesion and migration. After accelerated deterioration in a high-temperature environment, the specimens were evaluated by peeling tests. The peel strengths of adhesives S1-S6 and comparative adhesives C1-C3 are summarized in Table 9 below. [Table 10]
[0245] The data are for the present invention containing micromonomer components and graft copolymer structures. The adhesive exhibits superior adhesion to low surface energy substrates even after severe accelerated aging conditions at high temperatures. The results clearly show that the adhesive has excellent peel adhesion.
[0246] Not all of the features described in the general description or examples above are required, and no specific features may be required. Some of the functions described may not be necessary and may perform one or more functions in addition to those described. Furthermore, the order in which the functions are listed does not necessarily mean that they can be performed in the same order. This is not the order in which they should be listed.
[0247] Benefits, other advantages, and solutions to problems have been described above with regard to specific embodiments. However, benefits, advantages, solutions to problems, and any benefits, advantages or Any feature or features that may cause the solution to occur or become more prominent are either or any claim's key, essential, or essential features. isn't it.
[0248] The specification and illustrations of the embodiments set forth herein are provided to provide a general understanding of the structure of the various embodiments. The specification and examples are intended to provide a thorough understanding of the structures or A comprehensive and comprehensive description of all elements and features of the apparatus and systems that use the method Separate embodiments are also not intended to serve as a single embodiment. Conversely, for brevity, some embodiments may be provided in combination in the context of a single embodiment. The various features disclosed may also be provided separately or in any subcombination. Furthermore, references to values stated in ranges include any and all values within that range. Many other embodiments will be apparent to those skilled in the art upon reading the present disclosure. so that structural replacements, logical replacements, or other modifications can be made without the need for modification of other The embodiments may be used and derived from this disclosure. Therefore, this disclosure is not limiting. It should be considered exemplary.
Claims
1. An adhesive comprising an adhesive construction and an adhesive composition, the adhesive construction comprising: and the adhesive composition comprises a copolymer, At least about 1% by weight and no more than 40% by weight of the adhesive composition. A chromium monomer component, At least about 50% by weight and no more than about 98% by weight based on the total weight of the adhesive composition and a (meth)acrylic polymer component A of the formula: At least about 0.1 wt. % and not less than about 30 wt. % based on the total weight of the adhesive composition. and a tackifier component below, The macromonomer component has a weight average molecular weight of at least 1000 g / mol. 、 the macromonomer component has a glass transition temperature of at least about 40° C.; The (meth)acrylic polymer component A has a glass transition temperature (Tg) of about 20° C. or less. The adhesive comprising:
2. The graft copolymer of the adhesive construction comprises a backbone portion and a graft side chain portion. the main chain portion contains the (meth)acrylic polymer component A, and the graft side chain The adhesive of claim 1 , wherein a portion comprises the macromonomer component.
3. The graft copolymer of the adhesive construction is formed via radiation initiated polymerization. The adhesive according to claim 1 or 2.
4. The (meth)acrylic polymer component A is At least about 0.1% by weight based on the total weight of the (meth)acrylic polymer component A and about 10% by weight or less of monomer component a1 having pendant hydrogen bonding groups. Monomer component a1 comprising an ethylenically unsaturated functional monomer; At least about 80% by weight based on the total weight of the (meth)acrylic polymer component A and about 99% by weight or less of monomer component a2, comprising an ethylenically unsaturated monomer; and a monomer component a2. The adhesive described.
5. The monomer component a1 is an acid-containing (meth)acrylic monomer (acrylic acid, methacrylic acid acid, 2-carboxyethyl acrylate, etc.), hydroxy-containing (meth)acrylic monomers -(2-hydroxyethyl (meth)acrylate), primary, secondary, or tertiary amine Nitrogen-containing monomers having a 3-amino group and primary, secondary, or tertiary amide groups comprising an ethylenically unsaturated functional monomer selected from the group consisting of nitrogen-containing monomers; The adhesive of claim 4.
6. The monomer component a2 is represented by the formula C=C(R 2 ) (COOR 1 ) acrylic ester wherein R1 is an alkyl group containing 1 to 24 carbons and R2 is H or The adhesive of claim 4 which is chilled.
7. The macromonomer component is a (meth)acrylic monomer having a pendant alicyclic functional group. wherein the macromonomer component is polymerized in a free radical polymerization process. The adhesive according to claim 1 or 2, wherein
8. The tackifier component is C5, C9, C5 / C9, dicyclopentadiene, terpene, or hydrogenated resins thereof, or a combination thereof. Adhesive included.
9. 1. A method of forming an adhesive, the method comprising: providing a pre-adhesive mixture, the pre-adhesive mixture comprising: At least about 1% by weight and about 40% by weight, based on the total weight of the pre-adhesive mixture The following pre-adhesive macromonomer components have a molecular weight of at least about 1000 g / mol: weight, and a glass transition temperature of at least about 40° C. Ingredients and At least about 50% by weight and at least about 98% by weight based on the total weight of the pre-adhesive mixture. % or less of a pre-adhesive (meth)acrylic polymer component A, a pre-adhesive (meth)acrylic polymer component A having a transition temperature (Tg); At least about 0.1% by weight and at least about 30% by weight based on the total weight of the pre-adhesive mixture. % or less of a pre-adhesive tackifier component; mixing the pre-adhesive mixture; polymerizing the pre-adhesive mixture to form the adhesive; The adhesive comprises an adhesive structure and an adhesive composition, the adhesive structure comprising a graft copolymer. and polymerizing the polymer.
10. The pre-adhesive (meth)acrylic polymer component A is At least about 0.05 wt. .1% by weight and up to about 10% by weight of pre-adhesive monomer component a1, Pre-adhesive monomer component a, which comprises an ethylenically unsaturated functional monomer having a hydrogen bonding group 1 and at least about 8% by weight of the pre-adhesive (meth)acrylic polymer component A; 0% and up to about 99% by weight of pre-adhesive monomer component a2, A reaction product of a polymerizable material comprising: a pre-adhesive monomer component a2, which comprises a saturated monomer; The method of claim 9, comprising the step of:
11. The pre-adhesive monomer component a1 is an acid-containing (meth)acrylic monomer (acrylic acid, Methacrylic acid, 2-carboxyethyl acrylate, etc.), hydroxy-containing (meth)acrylic Monomer (2-hydroxyethyl (meth)acrylate), primary, secondary, or Nitrogen-containing monomers having a tertiary amino group, and primary, secondary, or tertiary amides an ethylenically unsaturated functional monomer selected from the group consisting of nitrogen-containing monomers having a group The method of claim 10, comprising:
12. The pre-adhesive monomer component a2 is represented by the formula C=C(R 2 ) (COOR 1 ) Acrylic wherein R1 is an alkyl group containing 1 to 24 carbons; 11. The method of claim 10, wherein 2 is H or methyl.
13. The pre-adhesive macromonomer component is a (meth)acrylic acid having a pendant alicyclic functional group. and the pre-adhesive macromonomer component comprises a copolymer monomer, the copolymer being polymerized by a free radical polymerization process.
10. The method of claim 9, wherein the polymer is capable of being polymerized in a gas phase.
14. The pre-adhesive tackifier component is C5, C9, C5 / C9, dicyclopentadiene, 10. The composition according to claim 9, comprising a terpene, or a hydrogenated resin thereof, or a combination thereof. The method described.
15. 1. A monolayer foam tape comprising: The adhesive structure includes a foam core having hollow microspheres in the adhesive. and an adhesive composition, the adhesive structure comprising a graft copolymer, the adhesive The composition comprises: At least about 1% by weight and no more than 40% by weight of the adhesive composition. A chromium monomer component, At least about 50% by weight and no more than about 98% by weight based on the total weight of the adhesive composition and a (meth)acrylic polymer component A of the formula: At least about 0.1 wt. % and not less than about 30 wt. % based on the total weight of the adhesive composition. and a tackifier component below, The macromonomer component has a weight average molecular weight of at least 1000 g / mol. 、 the macromonomer component has a glass transition temperature of at least about 40° C.; The (meth)acrylic polymer component A has a glass transition temperature (Tg) of about 20° C. or less. A single layer foam tape having
Citation Information
Patent Citations
Adhesive tape
JP1993017726A
Adhesive composition and optical member using the same
JP2010150400A
Acrylic adhesive composition for light-shielding double-sided adhesive member, light-shielding double-sided adhesive member and image display device
JP2017014461A
Photocurable composition, pressure-sensitive adhesive sheet, pressure-sensitive adhesive sheet laminate, cured product, laminate for forming image display device, and image display device
WO2018101252A1